Nanowebs for removing contaminants from aqueous solutions, kits therefor, and methods of their use

CN113382967BActive Publication Date: 2026-10-27CARBONET NANOTECHNOLOGIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980090512.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-05
Filing Date
2019-12-03
Publication Date
2026-10-27
Estimated Expiration
2039-12-03

Smart Images

  • Figure BDA0003182809980000311
    Figure BDA0003182809980000311
  • Figure BDA0003182809980000312
    Figure BDA0003182809980000312
  • Figure BDA0003182809980000313
    Figure BDA0003182809980000313
Patent Text Reader

Abstract

Provided are nanonets comprising a) surfactant aggregates having an average aggregate diameter; and b) a polymer having an average particle diameter that is equal to or less than the average aggregate diameter, wherein the nanonet has a diameter that is greater than the average particle diameter. Also provided are kits therefor and methods of using the nanonets to sequester non-aqueous moieties from aqueous solutions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of chelation, and more particularly to the field of chelating materials from aqueous environments. Background Technology

[0002] The decontamination and disposal of organic waste (such as sewage sludge, animal excrement, food processing waste, fracturing fluid, oil and gas, and other industrial wastewater) raises concerns for both the environment and public health. The treatment and disposal of contaminated water has significant social, environmental, and economic impacts. Currently, residual wastewater sludge is typically digested, incinerated, stockpiled in landfills, returned to the same environment, or used as fertilizer through the application of residual biological solids to agricultural land.

[0003] Encapsulating inorganic particles with polymers has been demonstrated (E. Bourgeat-Lami and E. Duguet: Polymer encapsulation of inorganic particles; in Functional coatings, SKGhosh (ed.); 2006, Wiley-VCH, Weinheim; Chapter 4, pp. 85-152). In biomedical applications, coatings of inorganic nanoparticles with polymers or encapsulating them in polymer matrices or detergent layers are important for properties such as solubilization (R. Ladj et al., Polymer encapsulation of inorganic nanoparticles for biomedical applications; Internat. J. Pharm. 2013(458) 230-241). In the fields of physics and engineering, magnetic fluids composed of magnetic nanoparticles coated with polymers and / or surfactants have been studied to stabilize the particles in the host liquid. Various synthetic methods for preparing such systems have been disclosed (e.g., J. Sommertune et al., Polymer / Iron oxide nanoparticles composites – a straight forward and scalable synthesis approach; Int. J. Mol. Sci. 2015(16) 19752-19768). Summary of the Invention

[0004] This invention is based at least in part on the following: nanoweb formation depends on the average aggregate diameter of the surfactant, and the length of the surrounding polymer determines the minimum surfactant aggregate diameter size for nanoweb formation. Contrary to solubilization studies of lipid bilayers with styrene-maleic acid polymers, the association of surfactants with polymers does not exclusively lead to a reduction in surfactant aggregate size. Instead, the combination of polymer and surfactant aggregates can result in a combined aggregate that is larger or smaller than the individual surfactant aggregates in solution. In the latter case, the polymer can cause relatively large surfactant aggregates to dissociate into smaller surfactant aggregates and polymer-associated aggregates. Furthermore, utilizing longer polymer lengths for nanoweb formation can lead to accelerated or delayed flocculation, which can facilitate the removal of precipitated nanowebs by physical separation or enhanced contact in the treated fluid. Therefore, nanowebs composed of polymers of varying molecular weights can be advantageous when applied to various wastewater treatment processes.

[0005] In an exemplary embodiment, a kit is provided for chelating non-aqueous fractions from an aqueous solution, the kit comprising: a) surfactant aggregates having an average aggregate diameter; b) a polymer having an average particle size equal to or less than the average aggregate diameter; and c) a precipitant, provided that the surfactant is selected from Triton X-100. TM Triton X-305 TM When N-dodecyl-β-D-maltodextrin (DDM), sodium oleate, sodium cholate, sodium deoxycholate (DOC), β-octyl glucoside (β-OG), or lauryl dimethylamine n-oxide (LDAO) are used, the polymer should not be selected from: SMA-2000 TM SMA-2021 TM And diisobutylene-co-maleic acid (DIBMA).

[0006] In an exemplary embodiment, a kit described herein is provided, wherein the precipitant is selected from: cation generators, cations, acids, divalent cations, trivalent cations, and mixtures thereof.

[0007] In an exemplary embodiment, a kit described herein is provided, wherein the precipitant is selected from acetic acid, malic acid, citric acid, tartaric acid, fumaric acid, lactic acid, hydrochloric acid, sulfuric acid, and phosphoric acid.

[0008] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is selected from: anionic surfactants, nonionic surfactants, sugar-derived surfactants, glycidyl-derived surfactants, fatty acid alcohol-derived surfactants, nonionic surfactants, sugar polyoxyethylene combination surfactants, sugar ester surfactants, sulfonated sugar surfactants, aldose amide surfactants, amide sugar surfactants, amino alcohol surfactants, amino acid surfactants, polyol surfactants, 1,2-diol surfactants, and amphoteric surfactants.

[0009] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is a nonionic surfactant.

[0010] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is an ionic surfactant.

[0011] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is an anionic surfactant.

[0012] In an exemplary embodiment, a kit described herein is provided in which the surfactant has a neutral charge.

[0013] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is an uncharged surfactant.

[0014] In an exemplary embodiment, a kit described herein is provided in which the surfactant is soluble in water.

[0015] In an exemplary embodiment, a kit described herein is provided in which the surfactant is insoluble in water.

[0016] In an exemplary embodiment, a kit described herein is provided, wherein the polymer is a long polymer.

[0017] In an exemplary embodiment, a kit described herein is provided, wherein the polymer has a molecular weight of at least 1,500 Da.

[0018] In an exemplary embodiment, a kit described herein is provided, wherein the polymer has a molecular weight of at least 26,000 Da.

[0019] In an exemplary embodiment, a kit described herein is provided, wherein the polymer has a molecular weight of at least 100,000 Da.

[0020] In an exemplary embodiment, a kit described herein is provided, wherein the polymer has a molecular weight of at least 125,000 Da.

[0021] In an exemplary embodiment, a kit described herein is provided, wherein the polymer is an amphiphilic polymer.

[0022] In an exemplary embodiment, a kit described herein is provided, wherein the polymer comprises an alkyl chain having a length of at least 8 carbon atoms.

[0023] In an exemplary embodiment, a kit described herein is provided, wherein the polymer is a block copolymer.

[0024] In an exemplary embodiment, a kit described herein is provided in which the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 1:1 to about 4:1.

[0025] In an exemplary embodiment, a kit described herein is provided in which the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 1:1 to about 3:1.

[0026] In an exemplary embodiment, a kit described herein is provided in which the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 2:1 to about 3:1.

[0027] In an exemplary embodiment, a kit described herein is provided in which the polymer comprises a hydrophobic group to a hydrophilic group ratio of approximately 2:1.

[0028] In an exemplary embodiment, a kit described herein is provided in which the polymer comprises a hydrophobic group to a hydrophilic group ratio of approximately 3:1.

[0029] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is selected from: octylphenol ethoxylate, nonylphenol ethoxylate, PGL1, PGL2, PGL3, PGL4, PGL5, Triton X-45. TM Triton X-100 TM Triton X-305 TM Sodium oleate, LDAO and their mixtures.

[0030] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is a mixture of PGL5 and sodium oleate.

[0031] In an exemplary embodiment, a kit described herein is provided, wherein the surfactant is a mixture of PGL5 and potassium oleate.

[0032] In an exemplary embodiment, a kit described herein is provided, wherein the polymer is selected from: SMA-725 TM SMA-2000 TMSMA-3000 TM SMA-2021 TM Polymethyl methacrylate, DIBMA, styrene urethane block copolymer and styrene maleimide block copolymer.

[0033] In an exemplary embodiment, a kit as described herein is provided, wherein the polymer is SMA-725. TM .

[0034] In an exemplary embodiment, a kit described herein is provided in which at least a portion of the polymer is hydrolyzed.

[0035] In an exemplary embodiment, a nanonet is provided comprising: a) surfactant aggregates having an average aggregate diameter; and b) a polymer having an average particle size equal to or less than the average aggregate diameter, provided that the surfactant is selected from: Triton X-100. TM Triton X-305 TM When N-dodecyl-β-D-maltodextrin (DDM), sodium oleate, sodium cholate, sodium deoxycholate (DOC), β-octyl glucoside (β-OG), or lauryl dimethylamine n-oxide (LDAO) are used, the polymer should not be selected from: SMA-2000 TM SMA-2021 TM And diisobutylene-co-maleic acid (DIBMA).

[0036] In an exemplary embodiment, a nanomesh as described herein is provided, wherein the nanomesh has a diameter greater than the average polymer particle size.

[0037] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is selected from: anionic surfactants, nonionic surfactants, sugar-derived surfactants, glycidyl-derived surfactants, fatty acid alcohol-derived surfactants, nonionic surfactants, sugar polyoxyethylene combination surfactants, sugar ester surfactants, sulfonated sugar surfactants, aldose amide surfactants, amide sugar surfactants, amino alcohol surfactants, amino acid surfactants, polyol surfactants, 1,2-diol surfactants, and amphoteric surfactants.

[0038] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is a nonionic surfactant.

[0039] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is an ionic surfactant.

[0040] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is an anionic surfactant.

[0041] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant has a neutral charge.

[0042] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is an uncharged surfactant.

[0043] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is soluble in water.

[0044] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is insoluble in water.

[0045] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer is a long polymer.

[0046] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer has a molecular weight of at least 1,500 Da.

[0047] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer has a molecular weight of at least 26,000 Da.

[0048] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer has a molecular weight of at least 100,000 Da.

[0049] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer has a molecular weight of at least 125,000 Da.

[0050] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer is an amphiphilic polymer.

[0051] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer comprises alkyl chains having a length of at least 8 carbon atoms.

[0052] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer is a block copolymer.

[0053] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 1:1 to about 4:1.

[0054] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 1:1 to about 3:1.

[0055] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 2:1 to about 3:1.

[0056] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of approximately 2:1.

[0057] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of approximately 3:1.

[0058] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is selected from: octylphenol ethoxylate, nonylphenol ethoxylate, PGL1, PGL2, PGL3, PGL4, PGL5, Triton X-45. TM Triton X-100 TM Triton X-305 TM Sodium oleate, LDAO and their mixtures.

[0059] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is a mixture of PGL5 and sodium oleate.

[0060] In an exemplary embodiment, a nanonet as described herein is provided, wherein the surfactant is a mixture of PGL5 and potassium oleate.

[0061] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer is selected from: SMA-725 TM SMA-2000 TM SMA-3000 TM SMA-2021 TM Polymethyl methacrylate, DIBMA, styrene urethane block copolymer and styrene maleimide block copolymer.

[0062] In an exemplary embodiment, a nanonet as described herein is provided, wherein the polymer is SMA-725. TM .

[0063] In an exemplary embodiment, a nanonet as described herein is provided, wherein at least a portion of the polymer is hydrolyzed.

[0064] In an exemplary embodiment, a nanonet as described herein is provided, which further includes a chelated non-aqueous portion.

[0065] In an exemplary embodiment, a nanonet as described herein is provided, wherein the chelated non-aqueous portion is an iron portion.

[0066] In an exemplary embodiment, a method is provided for chelating a non-aqueous portion from an aqueous solution, the method comprising: a) adding a surfactant aggregate having an average aggregate diameter to an aqueous solution containing the non-aqueous portion; and b) adding a polymer having an average particle size (the average particle size being equal to or less than the average aggregate diameter) to the aqueous solution containing the non-aqueous portion, thereby forming a treated aqueous solution, provided that the surfactant is selected from: Triton X-100 TM Triton X-305 TM When N-dodecyl-β-D-maltodextrin (DDM), sodium oleate, sodium cholate, sodium deoxycholate (DOC), β-octyl glucoside (β-OG), or lauryl dimethylamine n-oxide (LDAO) are used, the polymer should not be selected from: SMA-2000 TM SMA-2021 TM And diisobutylene-co-maleic acid (DIBMA).

[0067] In an exemplary embodiment, the method described herein is provided, which further includes adding a precipitant to a treated aqueous solution.

[0068] In exemplary embodiments, the methods described herein are provided, which further include mixing.

[0069] In an exemplary embodiment, the method described herein is provided, which further includes removing solid particles from a treated aqueous solution.

[0070] In exemplary embodiments, methods described herein are provided, wherein the removal of solid particles includes at least one selected from: filtration, centrifugation, gravity separation, flotation, skimming, and electromagnetic attraction.

[0071] In exemplary embodiments, the methods described herein are provided, wherein the surfactant is selected from: anionic surfactants, nonionic surfactants, sugar-derived surfactants, glycidyl-derived surfactants, fatty acid alcohol-derived surfactants, nonionic surfactants, sugar polyoxyethylene combination surfactants, sugar ester surfactants, sulfonated sugar surfactants, aldose amide surfactants, amide sugar surfactants, amino alcohol surfactants, amino acid surfactants, polyol surfactants, 1,2-diol surfactants, and amphoteric surfactants.

[0072] In an exemplary embodiment, the method described herein is provided, wherein the surfactant is a nonionic surfactant.

[0073] In an exemplary embodiment, the method described herein is provided, wherein the surfactant is an anionic surfactant.

[0074] In an exemplary embodiment, a method described herein is provided in which the surfactant has a neutral charge.

[0075] In an exemplary embodiment, the method described herein is provided, wherein the surfactant is an uncharged surfactant.

[0076] In an exemplary embodiment, a method described herein is provided in which the surfactant is soluble in water.

[0077] In an exemplary embodiment, a method described herein is provided in which the surfactant is insoluble in water.

[0078] In an exemplary embodiment, the method described herein is provided, wherein the polymer is a long polymer.

[0079] In an exemplary embodiment, the method described herein is provided, wherein the polymer has a molecular weight of at least 1,500 Da.

[0080] In an exemplary embodiment, the method described herein is provided, wherein the polymer has a molecular weight of at least 26,000 Da.

[0081] In an exemplary embodiment, the method described herein is provided, wherein the polymer has a molecular weight of at least 100,000 Da.

[0082] In an exemplary embodiment, the method described herein is provided, wherein the polymer has a molecular weight of at least 125,000 Da.

[0083] In an exemplary embodiment, the method described herein is provided, wherein the polymer is an amphiphilic polymer.

[0084] In an exemplary embodiment, a method described herein is provided, wherein the polymer comprises an alkyl chain having at least eight carbon atoms.

[0085] In an exemplary embodiment, the method described herein is provided, wherein the polymer is a block copolymer.

[0086] In an exemplary embodiment, the method described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 1:1 to about 4:1.

[0087] In an exemplary embodiment, the method described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of about 1:1 to about 3:1.

[0088] In an exemplary embodiment, a method described herein is provided in which the polymer comprises hydrophobic groups in a ratio of about 2:1 to about 3:1.

[0089] In an exemplary embodiment, the method described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of approximately 2:1.

[0090] In an exemplary embodiment, the method described herein is provided, wherein the polymer comprises a hydrophobic group to a hydrophilic group ratio of approximately 3:1.

[0091] In an exemplary embodiment, the method described herein is provided, wherein the surfactant is selected from: octylphenol ethoxylate, nonylphenol ethoxylate, PGL1, PGL2, PGL3, PGL4, PGL5, Triton X-45. TM Triton X-100 TM Triton X-305 TM Sodium oleate, LDAO and their mixtures.

[0092] In an exemplary embodiment, a method described herein is provided, wherein the surfactant is a mixture of PGL5 and sodium oleate.

[0093] In an exemplary embodiment, a method described herein is provided, wherein the surfactant is a mixture of PGL5 and potassium oleate.

[0094] In an exemplary embodiment, the method described herein is provided, wherein the polymer is selected from: SMA-725 TM SMA-2000 TM SMA-3000 TM SMA-2021 TM Polymethyl methacrylate, DIBMA, styrene urethane block copolymer and styrene maleimide block copolymer.

[0095] In an exemplary embodiment, the method described herein is provided, wherein the polymer is SMA-725. TM .

[0096] In an exemplary embodiment, a method described herein is provided in which at least a portion of the polymer is hydrolyzed.

[0097] In an exemplary embodiment, a method is provided for chelating a non-aqueous portion from an aqueous solution, the method comprising adding a nanonet as described herein to an aqueous solution containing the non-aqueous portion to form a treated aqueous solution.

[0098] In an exemplary embodiment, the method described herein is provided, which further includes adding a precipitant to a treated aqueous solution.

[0099] In exemplary embodiments, the methods described herein are provided, and hybridization is also included.

[0100] In exemplary embodiments, the methods described herein are provided, which also include the removal of solid particles from a treated aqueous solution.

[0101] In exemplary embodiments, methods described herein are provided, wherein the removal of solid particles includes at least one selected from: filtration, centrifugation, gravity separation, flotation, skimming, and electromagnetic attraction.

[0102] Other aspects and features of the invention will become apparent to those skilled in the art after reading the following description of specific embodiments of the invention in conjunction with the accompanying drawings. Attached Figure Description

[0103] In the accompanying drawings illustrating aspects of the invention

[0104] Figure 1: Structure-function relationship between polymer length and surfactant aggregate diameter in nanonetwork formation. A) Nanonetworks form when the polymer length and surfactant aggregate size are well matched. B) Nanonetworks do not form when the surfactant aggregate diameter is smaller than the diameter of the dense polymer particles. C) Nanonetworks form when large surfactant aggregates break down into multiple smaller nanonetworks. D) Nanonetworks form when large surfactant aggregates are stabilized by multiple polymers, leading to an overall increase in particle size.

[0105] Figure 2: Co-precipitation of the composite polymer and surfactant due to the addition of acid. A) Composed of different proportions of Triton X-305 TM Absorbance of the acid-precipitated nanonetwork formed by surfactants. Absorbance was measured at 540 nm as a representative of the scattered light from the flocculants. A long-chain polymer (SMA-725) was used. TM (triangular), short-chain polymers (SMA-2000) TM A) A) Forming a nanonet (square) and comparing it with a control (circular) containing only surfactant. B) As in A, using Triton X-100 TM As a surfactant. C) As with A, use Triton X-45. TM As a surfactant.

[0106] Figure 3: SMA-725 TMThe flocculation rate of the nanomesh was enhanced. A) Schematic diagram of distribution measurement. The total mass of flocculants from the precipitated nanomesh, after flocculation and flotation over time, solidified to a specified tube volume (top, top-middle, bottom-middle, and bottom: 100-75%, 75-50%, 50-25%, and 0-25%, respectively). B) Distribution of precipitated sodium oleate over time. C) Precipitated sodium oleate / SMA-725 TM Distribution of the nanomesh over time. D) Precipitated sodium oleate / SMA-2000 TM Distribution of the nanomesh over time. E) Removal of precipitate: sodium oleate (triangle pointing to the top of the page), sodium oleate, and sequentially added SMA-725. TM (Triangle pointing to the bottom of the page), Sodium oleate / SMA-725 TM Nano-mesh (circular) and sodium oleate SMA-2000 TM Solution of nanomesh (square). Solution clearance rate was measured by absorbance at 540 nm.

[0107] Figure 4 Nanomesh removal of dissolved iron under different concentrations of divalent cations. SMA-2000, formed using a specified surfactant in a 5:1 ratio (surfactant:polymer), was then used. TM The nanomesh was incubated with an iron solution overnight, then filtered and the iron content was quantified. As a control, the iron solution was filtered after either changing the pH or without treatment.

[0108] Figure 5 Nanomesh removal of dissolved iron under different concentrations of divalent cations. SMA-2000, formed using a specified surfactant in a 5:1 ratio (surfactant:polymer), was then used. TM The nanomesh was incubated with an iron solution for 10 minutes, then filtered and the iron content was quantified. As a control, the iron solution was filtered after either changing the pH or without treatment.

[0109] Figure 6: SMA-2000 at different buffer concentrations TM and SMA-725 TM Iron removal efficiency of nanomesh.

[0110] Figure 7: SMA-725 TM Nano-mesh from 100ppm iron solution (75:25Fe) 3+ :Fe 2+ Iron removal in

[0111] Figure 8 : A graph showing the effect of polymer and surfactant ratio on iron removal by sodium oleate nanonets.

[0112] Figure 9The effects of various nanomesh treatments on produced water samples (500 ppm oil, >100,000 TDS, >1,000 ppm divalent cations).

[0113] Figure 10 Quantitatively measured from the filtered treated produced water. Figure 9 The samples were filtered and quantified for oil and natural gas (O and G), total suspended solids (TSS), and total iron.

[0114] Figure 11: Using nanomesh OPGW (SMA-725) TM 75% sodium oleate, 25% polyglycerol-10 monostearate, 1:1 weight ratio of polymer:surfactant; 10-minute residence time, after filtration) to remove contaminants from the produced water. A) Iron removal, B) Color removal, and C) Turbidity removal.

[0115] Figure 12: Pollutant removal from produced water using OPGW nanofibers via dissolved air flotation and filtration. A) Total iron concentration before and after treatment. Total iron concentration was determined by the ferrazine method. B) Water color before and after treatment. Yellow color, indicating dissolved hydrocarbons and colloidal iron, was measured by absorbance at 350 nm. C) Turbidity before and after treatment. Turbidity was measured by absorbance at 540 nm.

[0116] Figure 13: A) Removal of extractable petroleum hydrocarbons with chain lengths of 10-32 carbons, where "beginning" is before treatment, "filtered" is without nanomesh but with filtration, and "filtered + nanomesh" is with both nanomesh and filtration. B) Removal of Zn and Fe from produced water. C) Removal of various metals from produced water.

[0117] Figure 14 Examples of polymer monomer units in hydrated and non-hydrated forms.

[0118] Figure 15: Using a typical surfactant a) Triton X-100 TM and b) Triton X-45 TM A nano-network is formed with styrene-maleic acid block copolymer.

[0119] Figure 16 Evolution of quantitative scoring methods for nanomesh.

[0120] Figure 17: Nanonet score for each SMA polymer combination.

[0121] Figure 18 Nanoscale scores of sulfonates, lactates, and tridecyl alcohol polyether sulfonates with different block copolymers.

[0122] Figure 19: Score formed with SMA polymer and with DIBMA nanonet.

[0123] Figure 20 Nanonet scores using different block copolymers at different HLB values.

[0124] Figure 21 The effect of alkyl chain length and hydrophilic head group length on the formation of nanonetworks using different surfactant head groups. The effect of alkyl chain length on the nanonetwork score of surfactants with the following head groups: A) Amino acid head groups (from top to bottom: N-dodecanoylmethionine, N-dodecanoylthreonine, N-decanoylmethionine, N-decanoylthreonine, N-octanoylmethionine, and N-octanoylthreonine), B) Sodium sulfonate head groups (from top to bottom: sodium dodecylbenzenesulfonate, sodium dodecanesulfonate, 1-octanesulfonate, p-toluene-1-sulfonate, and sodium pentanesulfonate), C) Ethyl glycol ether head groups (from top to bottom: hexaethylene glycol monododecyl ether, ... Heptaethylene glycol monododecyl ether, hexaethylene glycol monodecyl ether, and hexaethylene glycol monooctyl), D) Thioglycosides (from top to bottom: n-dodecyl-β-D-thiopyranoside, n-dodecyl-β-D-thiopyranoside, n-decyl-β-D-thiopyranoside, n-decyl-β-D-thiopyranoside, n-nonyl-β-D-thiopyranoside, n-octyl-maltoside, fluorinated, n-octyl-β-D-thiopyranoside, and n-heptyl-β-D-thiopyranoside). Hydrophilic head group size (indicated by HLB) for surfactants and E) Polyoxyethylene dehydrated sorbitol head group (from top to bottom: SPAN 20) TM TWEEN 65 TM TWEEN 85 TM TWEEN TM 80, TWEEN 60 TM TWEEN 40 TM With TWEEN 20 TM F) Phenyl polyethylene glycol head group (TRITON X-45) TM TRITON X-100 TM and TRITON X-305 TM The influence of nanomesh scores.

[0125] Figure 22 Used for screening to remove Cu from seawater 2+ A nano-network library of metal ions with anionic surfactants.

[0126] Figure 23 Used for screening to remove Cu from seawater 2+A nano-network of metal ions with nonionic surfactants.

[0127] Figure 24 Used for screening to remove Zn from seawater. 2+ A nano-network library of metal ions with anionic surfactants.

[0128] Figure 25 Used for screening to remove Zn from seawater. 2+ A nano-network of metal ions with nonionic surfactants.

[0129] Figure 26 SMA-725 added to calcium solution TM Settling curves for example batches of the BIOSOFT D-40 mixture. Quantitative floc settling over time was performed, and the data were fitted using an sigmoid function.

[0130] Figure 27 : Quantifying the apparent sedimentation velocities (t) of three different polymers 50 The bar chart shows the error bars in black.

[0131] Figure 28 Water parameters selected from treated and untreated produced water samples: A) Iron levels before and after treatment. B) Turbidity levels before and after treatment. C) Redox potential before and after treatment. D) Total dissolved solids before and after treatment. E) Bicarbonate levels before and after treatment.

[0132] Figure 29 Example: (A) Bar graphs showing the removal of iron from extracted water using nanomesh of different concentrations and (B) residual ClO2. Detailed Implementation

[0133] The nanonets described herein provide a means to effectively remove target contaminants by selecting appropriate polymer lengths and amounts based on surfactants best suited for their removal. In fact, any surfactant aggregate can be used in the nanonets, provided a suitable polymer is selected. Neutralization of the polymer results in the precipitation of the nanonet and the associated chelated contaminants. This is advantageous because the solid precipitate consisting of the nanonet and the associated chelated contaminants can be readily removed by physical separation methods. Non-limiting examples of physical separation methods include dissolved air flotation (DAF), sedimentation, filtration, centrifugation, gravity separation, flotation, skimming, electromagnetic attraction or repulsion, microfiltration, and nanofiltration. The relationship between polymer size and surfactant aggregate structure allows for the design of nanonet concepts tailored to selected contaminants suitable for conventional physical separation systems.

[0134] Surfactants are typically amphiphilic molecules with a hydrophilic head group and lipophilic / hydrophobic functional groups. Depending on the size and charge of the hydrophobic and hydrophilic head groups, surfactants can be soluble or insoluble in water. This balance is often referred to as the hydrophilic-lipophilic balance (HLB) (Griffin, William C. (1949), "Classification of Surface-Active Agents by 'HLB'", Journal of the Society of Cosmetic Chemists, 1(5):311–26), because the head group typically has an affinity for water, while the tail group has an affinity for lipids and oils. Surfactants can be insoluble in water, where they are typically used to prepare water-in-oil emulsions and have an HLB value <10, or soluble in water, where they are typically used to prepare oil-in-water emulsions and have an HLB value >10. Soluble surfactants typically form a Gibbs monolayer in aqueous solutions, where free surfactants are able to exchange from the bulk aqueous phase to the air-water interface. Conversely, insoluble surfactants form compressible Langmuir monolayers and do not exchange with the bulk aqueous phase or only slightly (Rogalska, E. et al., (2000). Formation and properties of Langmuir and Gibbsmonolayers: a comparative study using hydrogenated and partially fluorinated amphiphilic derivatives of mannitol. Chemistry and Physics of Lipids, 105(1), 71–91. doi:10.1016 / s0009-3084(99)00130-,9). Examples of lipids include phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol, and lecithin. Examples of soluble surfactants include Triton X-100. TM Sodium dodecyl sulfate and polyglycerol-10-laurate, all of which have HLB > 10. Examples of insoluble surfactants include SPAN 80. TM Or TWEEN 85 TM .

[0135] As used herein, the term "nanoweb" refers to particles formed through association between polymer and surfactant aggregates. Nanowebs self-assemble in an aqueous environment, are stable in aqueous solutions, and consist of i) polymer and ii) surfactant aggregates. Nanowebs maintain association at lower concentrations compared to surfactant aggregates without a polymer. The solution stability of nanowebs can be disrupted by adding suitable destabilizing materials. For example, but not limited to, destabilization of nanowebs containing a maleic acid component in the polymer can be induced by neutralizing charged carboxylic acid groups with acid. Without being theoretically limited, nanowebs are believed to result from interactions between the alkyl chains of the surfactant and the alkyl chains of the hydrophobic portion of the polymer. Typically, nanowebs are colloidal particles comprising an amphiphilic block copolymer and a surfactant. Amphiphilic block copolymers typically contain both hydrophilic and hydrophobic functional groups. Examples of hydrophilic functional groups include, but are not limited to, maleic acid, carboxylic acid, and amide-linked ethanol groups. Examples of hydrophobic functional groups include, but are not limited to, styrene and diisobutyl groups.

[0136] As used herein, “nano-mesh diameter” refers to the size of a nano-mesh in an aqueous environment as measured by dynamic light scattering. “Average nano-mesh diameter” refers to the average size of multiple nano-mesh sizes in an aqueous environment as measured by dynamic light scattering. The term “average nano-mesh diameter” may be used interchangeably with the terms “nano-mesh diameter” or “nano-mesh size” herein. Examples of how to measure the average nano-mesh diameter are provided in the Examples section of this document, but are not limiting.

[0137] As used herein, the term "aqueous solution" refers to a liquid environment in which water is the main component. Examples of aqueous solutions include, but are not limited to, wastewater, aqueous materials recovered from processes (e.g., sewage sludge, animal manure, food processing waste), oil and natural gas wastewater, used fracturing fluid, industrial wastewater, groundwater, etc.

[0138] As used herein, the term "precipitant" means any substance that is a cation and / or generates a cation when exposed to an aqueous environment. A substance that is a cation is a cation, and a substance that generates a cation when exposed to an aqueous environment is referred to herein as a "cation-generating agent." Examples of precipitants include, but are not limited to, acids, divalent cations, trivalent cations, acetic acid, malic acid, citric acid, tartaric acid, fumaric acid, lactic acid, hydrochloric acid, sulfuric acid, phosphoric acid, and mixtures thereof.

[0139] As used herein, the term "surfactant" means any surfactant containing a polar portion that is thermodynamically preferably solvated by a polar solvent and a nonpolar portion that is thermodynamically preferably solvated by a nonpolar solvent. The term "surfactant" is also intended to include anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants. Surfactants suitable for use in this invention form aggregates in aqueous solutions. Surfactants that do not form aggregates are not included in the term "surfactant" as used herein.

[0140] An "anionic surfactant" is a surfactant having a polar portion that ionizes in aqueous solution to form an anion (located on the polar portion attached to the nonpolar portion). A "cationic surfactant" is a surfactant having a cationic polar portion that ionizes in aqueous solution to form a cation (located on the polar portion attached to the nonpolar portion). A "nonionic surfactant" is a surfactant having a polar portion that does not ionize in aqueous solution. An "amphoteric surfactant" is a surfactant having separate cationic and anionic sites and being uncharged (e.g., non-limiting examples of zwitterions include dialkylammonium acetates or betaine dialkylsulfonyl acetates as zwitterions of N,N-dialkylammonium acetate). (From pg. 224-25, The Vocabulary of Organic Chemistry, Milton Orchin et al., Eds., John Wiley & Sons, 1980). Soap is a salt of anionic surfactants (usually fatty acids).

[0141] Those skilled in the art will understand that a wide range of suitable surfactants are used in this invention, see, for example, but not limited to, the following references: Drew Myers, Surfactant Science and Technology, VCH Publishers, Inc. 1988; Bordes, Romain, and Krister Holmberg. 2015. “Amino Acid-Based Surfactants – Do They Deserve More Attention?” Advances in Colloid and Interface Science 222(August):79–91; Essentials of Glycobiology. 3rd edition Varki A, Cummings RD, Esko JD, et al., editors. Cold Spring Harbor (NY): Cold Spring Harbor Laboratory Press; 2015–2017; Reference for definition: Zhang, X., Song, F., Taxipalati, M., Wei, W., & Feng, F. (2014). Comparative Study of Surface-Active Properties and Antimicrobial Activities. of DisaccharideMonoesters.PLoS ONE,9(12),e114845.doi:10.1371 / journal.pone.0114845;.RHBeck,NJKalff,and HWWRoper,European Patent Application,EP 536939,1993;V.Au,B.Harichian,A.Hung,and R.Vermeer,US 5872111 A, 1999; JJ Scheibel, DS Connor, REShumate, and LJ Charles, PCT Int Appl. WO 92 06984, 1992; CL Mehltretter, RLMellies, and JC Rankin, US patent 2670345, 1954; Z. Wang.United States patent US 7655611 B2, 2010; and Sari-Chmayssem N., Pessel F., Guégan JP, S. Taha, Mawlawi H., and Benvegnu T. Direct and one-pot conversion of polyguluronates andalginates into alkyl-L-guluronamide-based surfactant compositions, GreenChemistry; Novel surfactants and novel emulsifiers made from disaccharides.WO2006 / 100091; US ​​6,184,196 B1.SUCROSE BASED SURFACTANTS AND METHODS THEREOF; WO94 / 12511; and Safety Assessment of Alkyl Sultaines as Used inCosmetics.Christine Burnett.Cosmetic Ingredient Review,June 30,2017. .

[0142] Nanonetwork formation begins with the operation of a surfactant to form aggregates with an average aggregate diameter exceeding a threshold average particle size, which can be determined based on the average particle size of the polymer used in the nanonetwork composition. The surfactants described below can be used in embodiments of the nanonetworks described herein. In some cases, surfactants can be described based on their polar groups and their nonpolar groups. Common bonds between the polar and nonpolar components of a surfactant include, but are not limited to, ethers, amines, esters, phosphate esters, thioesters, and amide linkers.

[0143] Anionic surfactants

[0144] The polar sulfonate group can be attached to a nonpolar group to prepare surfactants of the following general formula: R-(SO3M) Z .

[0145] The sulfate polar group can be attached to a nonpolar group to prepare surfactants of the following general formula: R-(OSO3M) Z .

[0146] The polar carboxyl group can be attached to a nonpolar group to prepare surfactants of the following general formula: R-(COOM) Z .

[0147] The polar phosphate group can be attached to a nonpolar group to prepare surfactants of the following general formula: R-(OPO3M) Z .

[0148] The polar phosphite group can be attached to a nonpolar group to prepare surfactants of the following general formula: R-(PO3M) Z .

[0149] The polar group of α-sulfonated carboxylic acid can be attached to a nonpolar group to prepare surfactants of the following general formula: R—(CH(SO3M)COOM) Z R can be any one or more of lauric acid, palmitic acid, and stearic acid.

[0150] α-sulfonated carboxylic acid esters can have their polar groups attached to nonpolar groups to prepare surfactants of the following general formula: R—(CH(SO3M)COOR) 1 ) Z R can be any one or more of lauric acid, palmitic acid, and stearic acid. 1 It is a straight-chain or branched C1-C5 alkyl group. Z can be 1, 2, 3 or any combination thereof, and non-R groups can be located on the same carbon or different carbons in R.

[0151] The polar group of a sulfonate ester can be attached to a nonpolar group to prepare surfactants of the following general formula: R(COX(CH2)). n SO3M) Z (n can be in the range of 2 and 8, and X is O, NH, or -R) 1 .

[0152] Aryl amide sulfonates can have their polar groups attached to nonpolar groups to prepare surfactants of the following general formula: R(COXArSO3M) Z .

[0153] The xanthate polar group can be attached to a nonpolar group to prepare surfactants of the following general formula: R(OCS) - 2M) Z .

[0154] In any of the above formulas, M can be any monovalent cation, including but not limited to Na. + K + Li + .

[0155] Nonionic surfactants

[0156] The polar groups of polyethylene glycol can be attached to nonpolar groups to prepare surfactants of the following general formula: R(X(CH2CH2O) nCH2CH2OH) Z (X is O, S, or NH).

[0157] The polar groups of polypropylene glycol can be attached to nonpolar groups to prepare surfactants of the following general formula: R(X(CH2CH(CH3)O) n CH2CH(CH3)OH) Z (X is O, S, or NH).

[0158] The polar groups of diethylene glycolamines can be attached to nonpolar groups to prepare surfactants of the following general formula: (RX((CH2CH2O)) n CH2CH2OH)2(X is N).

[0159] The polar group of dipropylene glycolamine can be attached to a nonpolar group to prepare surfactants of the following general formula: (RX((CH2CH(CH3)O)) n CH2CH(CH3)OH)2(X is N).

[0160] In the chemical formulas shown above, R is straight-chain or branched, saturated, monounsaturated or polyunsaturated, aliphatic or aromatic, or polycyclic, and all possible combinations thereof. In some embodiments, the aromatic or non-aromatic ring is alkylated. In some embodiments, R may additionally contain O, N, S, and combinations thereof, and may be additionally functionalized with any one or more portions (e.g., carboxylic acids, carboxylate amides, thiocarboxylic acids, and combinations thereof). Typically, R has as few as 8 and as many as 40 carbon atoms. In some embodiments, R has as few as 7 or more carbon atoms. In some embodiments, R has 7 to 40 carbon atoms. In some embodiments, R has 8 to 40 carbon atoms. In some embodiments, R has 7 to 20 carbon atoms, or R has 8 to 20 carbon atoms, or R has 7 to 20 carbon atoms. In some embodiments, R has 7 to 18 carbon atoms, or R has 8 to 18 carbon atoms, or R has 9 to 18 carbon atoms.

[0161] When the above chemical formula includes the parameter "n", n can have the following values ​​unless some other value of n is indicated next to the specific chemical formula: in some embodiments, n can be in the range of 4 and 20, or in the range of 5 and 18, or in the range of 6 and 17, or in the range of 7 and 16, or in the range of 8 and 15.

[0162] For the chemical formulas that include the parameter "z", z can be 1, 2, 3 or any combination thereof, and non-R groups can be located on the same carbon in R or on different carbons of R groups.

[0163] For the above chemical formulas that include the parameter "Ar" in their chemical formulas, Ar can be benzene, p-toluene, or naphthalene.

[0164] In some embodiments of the surfactant represented by the above chemical formula, R can be cholic acid or a derivative thereof. In some embodiments, R can be any one or more of lauric acid, palmitic acid, and stearic acid. In some embodiments, R can contain up to five acetic acid functional groups. In other embodiments, R can be cocoyl. In some embodiments, R can be derived from fatty acids or fatty acid esters.

[0165] An embodiment using a surfactant having one of the nonionic polar groups described above uses a combination of alkyl groups, which can optimize the average aggregate size of the surfactant relative to the average particle size of the polymer to be used in the nanoweb composition, and further take into account the contribution of heteroatom-containing portions of the structure.

[0166] Sugar-derived nonionic surfactants, glycidyl-derived nonionic surfactants, and fatty acid alcohol-derived nonionic surfactants

[0167] Non-limiting examples of this type of surfactant include: polyethylene glycol derivatives of fatty acids, such as PEG derivatives of fatty acid amines. Specific examples of this type of surfactant include, but are not limited to: PEG-2 coconut amine, PEG-3 coconut amine, PEG-4 coconut amine, PEG-5 coconut amine, PEG-8 coconut amine, PEG-10 coconut amine, PEG-12 coconut amine, PEG-15 coconut amine, PEG-20 coconut amine, PEG-2 hydrogenated tallow amine, PEG-5 hydrogenated tallow amine, PEG-8 hydrogenated tallow amine, PEG-10 hydrogenated tallow amine, PEG-15 hydrogenated tallow amine, PEG-20 hydrogenated tallow amine, PEG... -30 hydrogenated tallow amine, PEG-40 hydrogenated tallow amine, PEG-50 hydrogenated tallow amine, PEG-2 laurylamine, PEG-2 oleamine, PEG-5 oleamine, PEG-6 oleamine, PEG-10 oleamine, PEG-15 oleamine, PEG-20 oleamine, PEG-25 oleamine, PEG-30 oleamine, PEG-12 palmitamine, PEG-2 rapeseed amine, PEG-2 soy amine, PEG-5 soy amine, PEG-8 soy amine, PEG-10 soy amine and PEG-15 soy amine.

[0168] Glycosyl functional groups

[0169] Acidic sugars: sugars having one or more hydroxyl groups substituted with carboxylic acids. Non-limiting examples of acidic sugars include gluconic acid and ascorbic acid.

[0170] Deoxyglycans: Sugars in which the hydroxyl group is replaced by hydrogen. Non-limiting examples of deoxyglycans include rhamnose, fucose, and deoxyribose.

[0171] C5 monosaccharides (furanoses): 5-carbon skeleton sugars that cyclize to form a 5-carbon ring. Non-limiting examples of C5 monosaccharides include fructose, ribose, xylose, arabinose, and lysolose.

[0172] C6-monosaccharides (pyranoses): 6-carbon skeletal sugars that cyclize to form a 6-carbon ring. Non-limiting examples of C6 monosaccharides include: glucose, mannose, allose, atroose, taurose, galactose, and pyranose.

[0173] Amino sugars: Sugar molecules in which the hydroxyl group has been replaced by an amine group. The functional group is most likely linked to a fatty acid via an amide bond, but those skilled in the art can also link amino sugars with a single hydroxyl group. Non-limiting examples of amino sugars include: galactosamine, glucosamine, sialic acid, N-acetyl-D-glucosamine, and mannosamine.

[0174] Aldosalamides: a class of glycosyl surfactants. Non-limiting examples of aldosalamide surfactants include: coconut oil D-glucamide.

[0175] Disaccharides: Disaccharides are sugars or carbohydrates prepared by linking two monosaccharides. Glycosidic bonds can form between any hydroxyl groups on the monosaccharides, resulting in many different combinations of bonds and stereochemistry, producing disaccharides with unique properties. Those skilled in the art can then react these disaccharides with free fatty acids to form disaccharide alkyl esters. Non-limiting examples of disaccharides include: sucrose, maltose, lactose, cellobiose, manniobiose, trehalose, lactulose, melitriose, xylobiose, melibiose, sophorose, and raffinose.

[0176] Polysaccharides: chains of more than two sugars linked together by glycosidic bonds. A non-limiting group of polysaccharides is alkyl polyglucosides (APGs).

[0177] Sugar alcohols: sugars in which the terminal aldehyde has been converted into an alcohol. Non-limiting examples of sugar alcohols include lactitol, sorbitol, isomaltitol, xylitol, erythritol, and mannitol.

[0178] Dehydrated sugar alcohols: sugar alcohols that have been dehydrated to form a cyclized lactone ring. Non-limiting examples of dehydrated sugar alcohols include: sorbitol, mannitol, xylitol, erythritol, furanoside, and furanose.

[0179] Methods for preparing glycosyl surfactants by adding alkyl chains and sugars:

[0180] Glycosidic bonds: Sugars can be linked to alkyl chains via glycosidic bonds. These bonds can be N, O, or S-linked, resulting in the substitution of the hydroxyl group on the sugar and its attachment to another carbon chain via an amine, ether, or thioether. All of the aforementioned sugar functional groups can be used to form glycosidic bonds with alkyl chains. Non-limiting examples of sugar-derived surfactants include: cocoyl glucoside (O-linked), octyl-glucosamine (N-linked), alkyl polyglucosides, 3-(butoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(pentoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(hexoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(heptoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(octoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(nonoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(decoxy) 3-(dodecyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(tetradecyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(hexadecyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(octadecyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(eicosyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(docodecyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(tetradecyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3- 3-(hexenoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(decenoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(dodecenoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(tetradecenoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(hexadecenoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(octadecenoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(eicosenoyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(teicosenoyloxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(teicosenoyloxy)-2-hydroxypropyl-β-D-galactopyranoside Glycosides, 3-(3-oxa-tetratekoxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(fluorododecanooxy)-2-hydroxypropyl-β-D-galactopyranoside, 3-(butoxy)-2-hydroxypropyl-β-D-glucopyranoside, 3-(octoxy)-2-hydroxypropyl-β-D-mannopyranoside, 3-(tetradecanooxy)-2-hydroxypropyl-β-D-lactoside, 3-(octadecanooxy)-2-hydroxypropyl-β-D-maltoside, 3-(octoxy)-2-hydroxypropyl-β-D-galactotrisaccharide, and 3-(dodecanooxy)-2-hydroxypropyl-β-D-cellotrisaccharide.

[0181] Sugar polyoxyethylene combined surfactant:

[0182] Non-limiting examples of this type of surfactant include: PEG-20 sorbitol cocoate, PEG-40 sorbitol diisostearate, PEG-2 sorbitol isostearate, PEG-5 sorbitol isostearate, PEG-20 sorbitol isostearate, PEG-40 sorbitol lanolinate, PEG-75 sorbitol lanolinate, PEG-10 sorbitol laurate, PEG-40 Sorbitol Laurate, PEG-44 Sorbitol Laurate, PEG-75 Sorbitol Laurate, PEG-80 Sorbitol Laurate, PEG-3 Sorbitol Oleate, PEG-6 Sorbitol Oleate, PEG-80 Sorbitol Palmitate, PEG-40 Sorbitol Perisostearate, PEG-40 Sorbitol Peroleate, PEG-3 Sorbitol Stearate, PEG- 6. Sorbitol stearate, PEG-40 sorbitol stearate, PEG-60 sorbitol stearate, PEG-20 sorbitol tetraoleate, PEG-30 sorbitol tetraoleate, PEG-40 sorbitol tetraoleate, PEG-60 sorbitol tetraoleate, PEG-60 sorbitol tetrastearate, PEG-20 sorbitol triisostearate, PEG-160 sorbitol triisostearate Isostearate, PEG-18 dehydrated sorbitol trioleate, sorbitol polyether-40 hexaoleate (formerly PEG-40 sorbitol hexaoleate), sorbitol polyether-50 hexaoleate (formerly PEG-50 sorbitol hexaoleate), sorbitol polyether-30 tetraoleate laurate (formerly PEG-30 sorbitol tetraoleate laurate), and sorbitol polyether-60 tetrastearate (formerly PEG-60 sorbitol tetrastearate).

[0183] Sugar ester surfactants:

[0184] Sugar functional groups condense with fatty acids to form sugar esters. It is assumed that all sugars are linked by ester bonds formed through the condensation reaction of the carboxylic acid of hydrolyzed maleic acid or free fatty acids with the alcohol group of the sugar. Various chemical methods exist for the formation of sugar fatty acid esters. Esterification can also occur enzymatically, most typically using a series of lipases. Non-limiting examples of sugar ester surfactants include: sorbitol monolaurate, mannitol oleate, glucose pentaacetate, maltitol laurate, raffinose isostearate, raffinose myristate, raffinose oleate, sucrose acetate isobutyrate, sucrose acetate / stearate, sucrose benzoate, sucrose cocoate, sucrose dilaurate, sucrose dipalmitate, sucrose distearate, sucrose hexasqualate, sucrose hexaoleate / hexapalmitate / hexastearate, sucrose hexapalmitate, sucrose laurate, sucrose myristate, sucrose octaacetate, sucrose oleate, sucrose palmitate, sucrose palmitate / stearate or sucrose stearate-palmitate, sucrose pentasqualate, sucrose pentahydroxystearate, sucrose polystyrene. Behenate, sucrose polycotyl oleate, sucrose polylaurate, sucrose polylinoleate, sucrose polyoleate, sucrose polysoylene oleate, sucrose polystearate, sucrose polystearate, sucrose stearate, sucrose tetrahydroxystearate, sucrose tetraisostearate, sucrose tetrastearate triacetate, sucrose tribenzene, sucrose trilaurate, sucrose tristearate, trehalose isostearate, dehydrated sorbitol monolaurate, dehydrated mannitol oleate, erythritol laurate, erythritol myristate, sucrose monolaurate, maltose monolaurate, lactose monolaurate; sucrose monodecanoate, maltose monodecanoate, lactose monodecanoate; and sucrose monocaprylate, maltose monocaprylate, lactose monocaprylate, monostearoyl xyloglucan, and fructose laurate.

[0185] Sulfonation of glycosyl surfactants:

[0186] Sulfonated sugar esters generally offer better solubility than plain sugar esters, allowing for increased solubility of long alkyl chain surfactants (stearates).

[0187] Amide sugar surfactants:

[0188] The characteristic of this type of surfactant lies in the amide linking a hydrophilic sugar head group to a lipophilic tail.

[0189] Amino alcohol surfactants:

[0190] These types of surfactants typically have the formula: RC(=O)-NH-X-OH, where R is usually C8 to C90. 40 Alkyl group, and X can be C1 to C2. 10 Alkyl chain. In some embodiments, R can be C4 to C5. 20 Alkyl, C5 to C 18Alkyl, C6 to C 17 Alkyl, C7 to C 16 Alkyl or C8 to C 15 Alkyl group. Non-limiting example of a surfactant: cocamide monoethanolamine, where R is C. 11 alkyl.

[0191] Amino acid surfactants:

[0192] Non-limiting examples of this type of surfactant include lauroyl glutamic acid, sodium cocoyl glycinate, N-dodecanoylaminomalonic acid, and N-dodecanoyl aspartic acid.

[0193] Polyol surfactants:

[0194] Molecules having more than two hydroxyl groups are polyols. They are relatively readily attached to fatty acids or other nonpolar groups containing carboxylic acid groups through the condensation of carboxylic acids and alcohols into fatty acid esters. Non-limiting examples of polar polyol groups that can be attached to desired nonpolar groups include polyglycerol and pentaerythritol. Non-limiting examples of polyol surfactants are polyglycerol laurate.

[0195] zwitterionic polar groups:

[0196] Non-limiting examples of zwitterionic polar groups include: glycine salts, betaine, sulfobetaine (sometimes called sulfobetaine), hydroxysulfobetaine, ethanolamide, and ammonium alkyl sulfates (general formula: RN). + (CH2)2XSO4 - X is an alkyl chain (which can have 1 to 6 carbons, most commonly 3 carbons) and phosphocholine. Non-limiting examples of this type of surfactant include: lysophospholipids, fos-choline, cocamidopropyl betaine, cocamidopropyl hydroxysulfonate betaine, cocamidopropyl hydroxysulfonate betaine, decanoyl sulfonate betaine, cetyl / lauryl / myristyl hydroxysulfonate betaine, cocamidopropyl hydroxysulfonate betaine, erucamide propyl hydroxysulfonate betaine, lauramide propyl hydroxysulfonate betaine, lauryl hydroxysulfonate betaine, lauryl sulfonate betaine, myristamide propyl hydroxysulfonate betaine, myristyl sulfonate betaine, oleamide propyl hydroxysulfonate betaine, and tartamide propyl hydroxysulfonate betaine, as well as lysophospholipid C.

[0197] The surfactants suitable for use in this invention have aggregate diameters. As used herein, the term "aggregate diameter" refers to the size of an aggregate of surfactant in aqueous conditions, as measured by dynamic light scattering. "Average aggregate diameter" refers to the average size of multiple surfactant aggregates in an aqueous environment, as measured by dynamic light scattering. The term "average aggregate diameter" may be used interchangeably with the term "aggregate diameter" herein. Examples of how to measure the average aggregate diameter are provided in the Examples section of this document, but are not limiting.

[0198] Surfactants that associate with non-aqueous portions are commonly used to stabilize contaminants in aqueous solutions. Modifying the head and tail regions of a surfactant can substantially alter the morphology of surfactant aggregates, the hydrophobic lipid balance of the molecules, and thus the ability of surfactant aggregates to bind to and stabilize various contaminants in solution. For example, changing the length of the alkyl chain of a surfactant can alter the hydrophobic lipid balance of the surfactant molecule, which can affect aggregate shape, the ability to dissolve oils in water, and / or the number of surfactant aggregates. Surfactants can also be used to increase the flotation efficiency of contaminants by increasing their association with microbubbles. However, when surfactant aggregates are used alone, they often remain in the water after treatment, making the resulting water chemically incompatible with many industrial processes, particularly those that may require water with high surface tension.

[0199] As used herein, the term "polymer" refers to a relatively high molecular weight substance that is at least partially soluble in an aqueous environment. Polymers are constructed by linking small molecules called monomer units together in sufficient numbers such that the addition or removal of one or more units does not substantially alter the properties of the polymer. A monomer unit is a group of atoms derived from a monomer that constitutes the repeating unit in a polymer (Milton Orchin et al., in Vocabulary of Organic Chemistry p. 518 (John Wiley & Sons, 1980)). Monomer units can be linked in a regular or irregular repeating pattern.

[0200] In some embodiments, the polymer in the nanomesh composition may comprise two different monomer units. In some embodiments, the polymer in the nanomesh composition may comprise three different monomer units. In some embodiments, the polymer in the nanomesh composition may comprise multiple different monomer units. In some embodiments, the polymer in the nanomesh composition may be composed of straight chains or branched chains. In some embodiments, some monomer units may be relatively more hydrophilic, while others may be relatively more hydrophobic.

[0201] In some embodiments, the different monomer units constituting the polymer alternate regularly, for example, --ABAB--. In some embodiments, the different monomer units constituting the polymer may alternate substantially in different patterns, for example, --AABAAB--. This type of alternation can be considered a block. In some embodiments, a larger number of monomer units constituting the polymer may be repeated in a larger sequence before the alternation of another monomer unit in the polymer. The greater the number of identical repeating monomer units, the larger the block in the polymer. In some embodiments of the polymer constituting the nanonetwork composition, the block comprises two first-type monomer units and one second-type monomer unit. In other embodiments, the block may comprise two first-type monomer units, one second-type monomer unit, and one third-type monomer unit.

[0202] In some embodiments, the polymer constituting the nanoweb composition has at least one hydrophilic monomer unit and at least one hydrophobic monomer unit. The polymer in the nanoweb composition may be made of a styrene-maleic acid copolymer. The polymer in the nanoweb composition may be a hydrolyzed styrene-maleic acid copolymer. In some embodiments, the polymer may be a hydrolyzed diisobutylene-maleic anhydride copolymer (DIB-co-maleic anhydride). Like SMA, DIB-co-maleic anhydride is insoluble in aqueous solution, but becomes soluble when at least a portion of the maleic anhydride monomer units are hydrolyzed to a dicarboxylic acid form. The following applies to each of SMA and DIB-co-maleic anhydride, and the resulting form containing a water-soluble dicarboxylic acid. It should be understood herein that SMA is generally used as an abbreviation for styrene-malic acid copolymer, and DIBMA as an abbreviation for diisobutylene-maleic anhydride copolymer, and such abbreviations are context-specific, and both abbreviations may refer to hydrolyzed and non-hydrolyzed forms of these copolymers, and those skilled in the art will readily be able to identify whether the copolymer is in a hydrolyzed form. The abbreviations hSMA and hDIBMA are typically used to refer to the hydrolyzed form of these copolymers.

[0203] SMA is generally insoluble in aqueous solutions. To increase the solubility of SMA, the polymer can be heated in an alkaline pH solution, causing at least a portion of the maleic anhydride units in the polymer to hydrolyze, thereby forming hSMA. This means that a portion of the repeating maleic anhydride units in hSMA is chemically converted into adjacent CH groups, each CH group bearing a side carboxylic acid group. Chemically, such repeating dicarboxylic acid units in hSMA can be represented as: –CH(COOH)—CH(COOH)-- or its salt form, wherein one or both of the adjacent carboxylic acid units can be in the form of a protonated acid or its salt. In some embodiments, the adjacent carboxylic acid units can be in the form of a salt having a single divalent or polyvalent cation. For example, divalent and polyvalent cations, such as, but not limited to, ammonium ions, calcium ions, magnesium ions, or ferrous or trivalent ferric ions.

[0204] In some embodiments of the nanoweb composition, the percentage of hydrolysis of SMA to HSMA (or DIB-co-maleic anhydride to hDIBMA) is the effective amount of polymer substantially dissolved in an aqueous solution under the conditions used to form the nanoweb. In some embodiments, substantially all maleic acid units are hydrolyzed to produce dicarboxylic acid repeating units in the polymer chain. In some embodiments, not all maleic acid units are hydrolyzed.

[0205] In some embodiments, at least one hydrophilic monomer unit is hydrolyzed to maleic acid or a salt thereof and has the general chemical formula [-CH(COR)]. 6 )CH(COR 7 The maleic anhydride is present in a sufficient quantity (through hydrolysis of some maleic anhydride monomer units) to dissolve the polymer in an aqueous solution at a concentration sufficient to form a nanoweb composition (see [link to relevant documentation]). Figure 14 When all maleic anhydride monomer units in a polymer are completely hydrolyzed (e.g., polymer 2000), R 6 and R 7 =OH (carboxylic acid functional group).

[0206] In some implementations, certain maleic anhydride monomer units in the polymer can be modified, thereby altering R. 6 R 7 Or any one or more of both. For example, R 6 R 7 Or either one or more of the two can be OR 1 OR 2 NHR 1 NHR 2 NR 1 2. NR 2 2 and SR 1Such modification can be achieved by any one or more substitution, displacement, or condensation reactions known to those skilled in the art, including but not limited to those described in the Examples section.

[0207] R 6 R 7 Or both, R 1 R 2 Alternatively, both can be side groups of maleic acid monomer units in polymers that functionalize the nanonetwork composition. For example, any R group in this paragraph can be hydrogen, C1-C... 40 The compounds are any one or more of the following: straight-chain or branched, saturated, monounsaturated or polyunsaturated, aliphatic or aromatic, polycyclic, sugars, pyridines, pyrimidines, purines, cyclodextrins, indole, isoindole, glycosides, and piperazines. In some embodiments, the aromatic ring is alkylated.

[0208] In some embodiments, the polymer has hydrophobic monomer units, and the hydrophobic monomers constituting the polymer include unsaturated carbon chains having one to ten additional carbon atoms. Examples include styrene, p-methylstyrene, chlorostyrene, 2-chlorostyrene, 4-chlorostyrene, fluorostyrene, bromostyrene, propylene, isobutylene, isoprene, and mixtures thereof.

[0209] In other embodiments, the hydrophobic monomer unit may be straight-chain or branched, saturated, monounsaturated or polyunsaturated, aliphatic ring, polycyclic, or aromatic ring having at least one aromatic ring. In some embodiments, the aromatic ring is alkylated. Typically, the hydrophobic monomer unit has as few as 3 and as many as 10 carbon atoms.

[0210] The polymers applicable to this invention have an average particle size. As used herein, “particle size” refers to the size of a polymer under aqueous conditions, as measured by dynamic light scattering. “Theoretical polymer diameter” refers to the theoretical minimum diameter of a dense polymer sphere that can be calculated as described below. “Average particle size” refers to the average size of a plurality of polymers in an aqueous environment, as measured by dynamic light scattering. The term “average particle size” may be used interchangeably with the term “particle size” herein. Examples of how to measure the average particle size are provided in the Examples section of this document, but are not limiting.

[0211] The polymer can be a long polymer or a short polymer. As used herein, the term "long polymer" refers to a polymer with a molecular weight greater than 40,000 g / mol and / or an elongation greater than 100 nm. As used herein, the term "short polymer" refers to a polymer with a molecular weight less than 40,000 Da and / or an elongation less than 100 nm.

[0212] In some embodiments, functional groups on the polymer suitable for the nanomesh interact with divalent and trivalent cations, such as maleic acid. The addition of divalent and trivalent cations neutralizes the negative charge of the carboxylic acid groups present on the maleic acid, thereby precipitating the polymer. The corresponding association between the maleic acid-functionalized block copolymer and the surfactant aggregates makes the surfactant aggregates sensitive to cations. Therefore, adding the nanomesh to a solution containing a high concentration of divalent and trivalent cations will precipitate the entire nanomesh and cation complex. In some cases, a suitably high concentration of monovalent cations can also precipitate the entire nanomesh and associated cation complex. The resulting precipitate is hydrophobic in nature and binds non-aqueous portions, such as hydrocarbons. Over time, the precipitate begins to flocculate, thus increasing in size and becoming more easily removed from the solution by physical means such as sedimentation or flotation. If the surfactant and polymer are added sequentially to a solution containing a high concentration of a polymer-specific precipitant, the binding and flocculation effect of the non-aqueous portion of the surfactant is lost because the polymer immediately precipitates into individual particles, and the surfactant component remains freely dissociated in the solution. In the presence of a precipitant that acts on the surfactant in the solution, the sequential addition of the polymer and detergent will result in the precipitation of the polymer and surfactant separately, and loss of flocculation effect.

[0213] An exemplary embodiment of the present invention provides a nanonet comprising:

[0214] a) Surfactant aggregates with an average aggregate diameter; and

[0215] b) Polymers having an average particle size equal to or less than the average aggregate diameter. The resulting nanonetwork typically has a diameter greater than the average particle size.

[0216] Other exemplary embodiments of the present invention provide a nanonet comprising:

[0217] a) Surfactant aggregates with an average aggregate diameter; and

[0218] b) Polymers having an average particle size equal to or smaller than the average aggregate diameter. The resulting nanowebs typically have a diameter larger than the average particle size. The following nanowebs are specifically excluded in these embodiments:

[0219] 1) The surfactant is selected from: Triton X-100 TM Triton X-305 TM N-Dodecyl-β-D-maltose (DDM), sodium oleate, sodium cholate, sodium deoxycholate (DOC), β-octyl glucoside (β-OG), and lauryl dimethylamine n-oxide (LDAO); and

[0220] 2) The polymer is selected from: SMA-2000 TM SMA-2021 TM And diisobutylene-co-maleic acid (DIBMA).

[0221] For clarity, the present invention includes a surfactant selected from Triton X-100. TM Triton X-305 TM The embodiments of DDM, sodium oleate, sodium cholate, DOC, β-OG and LDAO are provided, provided that the polymer is not exclusive and is only SMA-2000. TM SMA-2021 TM Or one of DIBMA. Similarly, the present invention includes polymers selected from SMA-2000. TM SMA-2021 TM The implementation scheme of DIBMA is provided that the surfactant is not exclusive and is only Triton X-100. TM Triton X-305 TM One of DDM, sodium oleate, sodium cholate, DOC, β-OG, or LDAO.

[0222] In some embodiments, the surfactant is not a phospholipid. In other embodiments, the surfactant is not a lipid.

[0223] Nanonetwork formation can be expected by selecting a ratio of surfactant average aggregate diameter to polymer average particle size of 1:≤1. Typically, a ratio of surfactant average aggregate diameter to polymer average particle size of 1:<1 is preferred, where <1 is close to 1 but still less than 1. This allows for the design of nanonetworks with a wide variety of surfactants and polymers, which are stable and readily incorporate large amounts of surfactant molecules. By increasing the trapping of surfactant molecules within the nanonetwork, it is also possible to select physical parameters that may be important for later-stage applications of the particles.

[0224] When selecting materials for preparing nanowebs, the surfactant aggregates preferably have an average aggregate diameter larger than the average particle size of the polymer. For a given polymer size, this limits the selection of suitable surfactants that can be incorporated into the nanowebs; the shorter the polymer, the more types of nanowebs can be formed. However, as the polymer length increases, nanosheets containing surfactants with an average aggregate diameter larger than or equal to the average particle size of the polymer can result in smaller, more stable nanosheets that can exhibit enhanced flocculation efficiency and / or flotation properties. Therefore, selecting longer polymers and choosing suitable surfactants based on the ratio of the average aggregate diameter to the average particle size of the selected polymer provides for the formation of stable nanowebs with advantageous properties.

[0225] Under preferred formation conditions, the polymer particles in the dense polymer clusters have an average particle size slightly smaller than the average aggregate diameter of the surfactant. In aqueous conditions and with a slightly excess of polymer, the surfactant and polymer will self-assemble into a nanonetwork, leading to an increase in precipitated substances in the solution. Figure 1A An example of this relationship is shown in the following embodiments, wherein SMA-2000 TM (4nm in diameter, 14nm in length) and Triton X-100 TM (5.3 nm in diameter, 16.6 nm in perimeter) formed a nanonet (5.1 nm in diameter, 16 nm in perimeter) at a 1:1 weight / weight ratio.

[0226] Surfactant aggregates may be too large to be surrounded by a single polymer chain. This can cause the original surfactant aggregates to break down into smaller nanonetworks. Figure 1C This is similar to the dissolution of SMA in lipid bilayers. JM, Koorengevel, MC M., Prokofyev, AV, Scheidelaar, S., van der Cruijsen, E.A.W., Dafforn, TR, Baldus, M., Killian. J. Detergent-free isolation of KcsA in nanodiscs. PNAS. Dec 2014, 111(52) 18607-18612). In the following examples, the distribution of surfactant between polymers is illustrated using PGL1, PGL1 in SMA-2000 TM and SMA-725 TMThe polymers dissolved into 25 nm particles (Table 4). However, multiple polymers can also associate around large surfactant aggregates, which in some cases can lead to an increase in the size of the nanonetwork compared to the average diameter of the surfactant aggregates. Figure 1D ).

[0227] For a given polymer length, the surfactant aggregates may also be too small. Figure 2A and Figure 2B (Triangle). However, while large surfactant aggregates can form nanonetworks with smaller polymers, surfactant aggregates that are too small will remain separate and will not form nanonetworks with larger polymers. For example, as described in the following examples, Triton X-100 TM and Triton X-305 TM The aggregates are all too small to be combined with the large SMA-725 TM The polymer effectively forms a nanonetwork, but can be combined with the smaller SMA-2000. TM Polymers form nanowebs. This is likely due to the free energy landscape controlling the association of amphiphilic molecules. Surfactant aggregates can form as the entropy cost of multimolecular assembly balances the free energy saved by shielding hydrophobic alkyl chains with aqueous solutions. This shielding of hydrophobic groups with water also occurs in SMA polymers, resulting in dense granular structures in buffered aqueous solutions. Dense polymer particles represent the smallest diameter conformation that the polymer can adopt. In the case of small surfactant aggregates and large polymers, the size increase of both surfactants and polymers due to their association would therefore be entropy-unfavorable and would not occur in the absence of other factors. Figure 1B Possible factors could include enthalpy contributions, such as hydrogen bonds, salt bridges, or electrostatic interactions between the surfactant and the polymer.

[0228] In some implementations, the nanomesh assembly can be determined using the following formula:

[0229]

[0230]

[0231] The diameter (D) of surfactant aggregates 聚集体 )=2x((nx V sur ) / π / 4x3) 1 / 3 , where V is the calculated volume of the surfactant monomer, and n is the number of surfactant molecules in the surfactant aggregate.

[0232] The diameter of dense polymer micelles (D) 聚合物 )=2x((n 嵌段 x V 嵌段) / π / 4x3) 1 / 3 , where V is the calculated volume of the polymer block and n is the number of blocks in a single polymer chain.

[0233] SMA-2000 TM Calculation of the diameter of dense polymers: Mw 嵌段 = 324 g / mol; (2 styrene molecules, 1 maleic acid molecule), Mw SMA2000 ≈7500g / mol

[0234] n 嵌段 =Mw 聚合物 / Mw 嵌段 ≈23;

[0235]

[0236]

[0237]

[0238] SMA-2021 TM Calculation of the diameter of dense polymers: Mw 嵌段 = 324 g / mol; (2 styrene molecules, 1 maleic acid molecule), Mw SMA2021 ≈22,000 g / mol

[0239] n 嵌段 =Mw 聚合物 / Mw 嵌段 ≈68

[0240]

[0241]

[0242]

[0243] SMA-725 TM Calculation of the diameter of dense polymers: Mw 嵌段 = 428 g / mol; (3 styrene, 1 maleic acid), Mw SMA725 ≈130,000 g / mol

[0244] n 嵌段 =Mw SMA725 / Mw 嵌段 ≈308

[0245]

[0246]

[0247]

[0248]

[0249] SMA-3000 TM Calculation of the diameter of dense polymers: Mw 嵌段 = 428 g / mol; (3 styrene, 1 maleic acid), Mw SMA3000 ≈9,000 g / mol

[0250] n 嵌段 =Mw SMA3000 / Mw 嵌段 ≈21

[0251]

[0252]

[0253]

[0254] Calculation of the diameter of SMA-IBE dense polymer: Mw 嵌段 = 220.2 g / mol; (1 styrene, 1 maleic acid), Mv SMA-IBE ≈65,000g / mol

[0255] n 嵌段 =Mv 聚合物 / Mw 嵌段 ≈295

[0256]

[0257]

[0258]

[0259] Calculation of the diameter of SMA-cumene-terminated dense polymer: Mw 嵌段 = 428 g / mol; (3 styrene, 1 maleic acid), Mw 枯烯 =152g / mol Mw SMA-枯烯 ≈1500g / mol

[0260] n 嵌段 =Mw SMA-枯烯 -Mw 枯烯 / Mw 嵌段 ≈3.1

[0261]

[0262]

[0263]

[0264] Calculation of the diameter of DIBMA dense polymer: Mw 嵌段 = 226 g / mol; (18 hydrogen atoms, 12 carbon atoms, 4 oxygen atoms), Mw DIBMA ≈12,000 g / mol

[0265] n 嵌段 =Mw DIBMA / Mw 嵌段 ≈53

[0266]

[0267]

[0268]

[0269] Ethanol-derived SMA-2000 TM Calculation of the diameter of dense polymers: Mw 嵌段 = 367 g / mol; (22 carbon atoms, 4 oxygen atoms, 1 nitrogen atom, 25 hydrogen atoms), Mw 乙醇衍生SMA2000 ≈8495g / mol

[0270] n 嵌段 =Mw 聚合物 / Mw 嵌段 ≈23;

[0271]

[0272]

[0273]

[0274] Triton X-100 TM Calculation of surfactant aggregate diameter:

[0275] (D 聚集体 )=2x((nx V sur )) / π / 4x3) 1 / 3

[0276]

[0277]

[0278] For Tx-100, D 聚集体 >D SMA2000 Predicting the formation of nanowebs. D 聚集体 <D SMA725 TM SMA725TM Not suitable for forming nanowebs. 聚集体 >D SMA2021 It is predicted that a nanonet will form.

[0279] Triton X-305 TM Calculation of surfactant aggregate diameter:

[0280] (D 聚集体 )=2x((nx V sur )) / π / 4x3) 1 / 3

[0281]

[0282]

[0283] For Triton X-305 TM D 聚集体 >D SMA2000 Using SMA-2000 TM Predicting the formation of nanowebs. D 聚集体 <D SMA725 Using SMA-725 TM Not suitable for forming nanowebs. 聚集体 >D SMA2021 It is predicted that a nanonet will form.

[0284]

[0285]

[0286] *It is assumed that fully dense polymers are typically spherical in shape.

[0287] In some exemplary embodiments of the present invention, the surfactant is selected from: PGL1, PGL2, PGL3, PGL4, PGL5, Triton X-45. TM Triton X-100 TM Triton X-305 TMSodium oleate, potassium oleate, LDAO, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan myristate, polyoxyethylene sorbitan stearate, polyoxyethylene sorbitan palmitate, lauramidopropyl betaine, cocoyl glycinate, glucose monolaurate, sucrose laurate, sucrose monooleate, sucrose palmitate, glyceryl monolaurate, fructose laurate, potassium oleate, oleic acid, palmitic acid, linoleic acid, and mixtures thereof. In some embodiments, the surfactant is a mixture of PGL5 and sodium oleate. In some embodiments, the surfactant is a mixture of PGL5 and potassium oleate.

[0288] In exemplary embodiments of the present invention, the polymer is a block copolymer. In some embodiments, the polymer has a hydrophobic group to hydrophilic group ratio of about 1:1 to about 4:1, about 1:1 to about 3:1, about 2:1 to about 3:1, or about 2:1. In some embodiments, the polymer is selected from: SMA-725 TM SMA 3000 TM SMA-2000 TM and SMA-2021 TM In some implementations, the polymer is SMA-725. TM .

[0289] The nanonets according to the invention can be prepared by mixing polymers and surfactants in an aqueous environment. Adding sufficient surfactant to achieve a concentrated micelle concentration (CMC) is generally advantageous. The nanonets can be prepared in a cleaner and / or sterile environment and then added to an aqueous solution for later processing, or they can be provided as a separate component in a kit for later mixing. The components of the kit can be mixed in a clean and / or sterile environment, or they can be mixed in situ to prepare the nanonets directly in the aqueous solution to be treated.

[0290] In exemplary embodiments, a method for treating produced water using the nanomesh described herein is provided. An example of such a method is injecting a solution of the nanomesh into a liquid stream. Injection can be performed by any method known to those skilled in the art, and is typically via an injector, such as a Venturi injector. The nanomesh solution can be actively pumped into the injector, or, if a suitable pressure drop is present, naturally drawn into the fluid stream by the Venturi effect. The nanomesh solution can be injected into the fluid stream alone, or simultaneously with natural gas or other water treatment agents. The nanomesh solution can also be injected via an injection coil, followed by injection through a static mixer. In such cases, it may be necessary to first dilute the nanomesh solution to promote mixing in the pipeline.

[0291] Example

[0292] The following examples illustrate some embodiments of the invention described herein. These examples do not limit the spirit or scope of the invention in any way.

[0293] In the following Examples 1 to 14, the following methods, reagents and materials were used.

[0294] Reagents and materials:

[0295] Unless otherwise stated, all chemicals were purchased from Sigma-Aldrich. TM Canada. Polyglycerol-10-palmitate (PGL5), polyglycerol-10-oleate (PGL1), polyglycerol-10-stearate (PGL3), polyglycerol-10-laurate 1 (PGL2) and 2 (PGL4) were purchased from Shandong Binzhou New Material Technology Co. TM The styrene-maleic anhydride block copolymer was purchased from Cray Valley Ltd. TM (SMA-2000 TM (or Jiaxing Huawen Chemical Co.) TM Ltd(SMA-725) TM ).

[0296] SMA-725 TM and SMA-2000 TM Preparation of concentrated polymer stock solutions

[0297] To prepare styrene-maleic acid copolymer, SMA-725 was first... TM Grind into a fine powder, and purchase SMA-2000 in powder form at the same time. TM Subsequently, 5% (wt / vol) of pre-hydrolyzed SMA-725 was added. TM and SMA-2000 TMIncubate at 80°C in 500 mM potassium hydroxide for 5 hours with stirring, or until the solution is clear. Pass the solution through a 10 μm filter to remove unhydrolyzed particles, then precipitate by adding 12 M HCl dropwise with stirring until pH ≤ 2. Filter the precipitated polymer (10 μm), wash three times with 100 mL of dilute HCl (50 mM), wash three times with 100 mL of ultrapure water, and then dry at room temperature for 72 hours. Prepare a concentrated polymer stock solution by resuspending 200 mg of the dried polymer in ultrapure water and adjusting the pH of the suspension to 7 by adding sodium hydroxide dropwise. Then adjust the resulting clear polymer solution to a final volume of 10 mL and a final concentration of 2% (wt / vol). Prepare all polymer stock solutions according to this procedure and dilute accordingly with distilled water before use.

[0298] The polymer stock solution prepared according to the above procedure is used in the examples described in the following sections; even if the polymer is only mentioned by its name or trade name.

[0299] Preparation of surfactant stock solutions.

[0300] Triton X-100 was prepared by mixing 300 mg of surfactant in 30 mL of ultrapure water. TM Triton X-305 TM and Triton X-45 TM Stock solutions. Stock solutions of PGL1, PGL3, or PGL5 were prepared by weighing 1 g, 500 mg, or 330 mg, respectively. The weighed amount of the selected surfactant was resuspended in 10 mL of ultrapure water and mixed using a hand-held homogenizer until emulsified to produce the respective PGL surfactant stock solution. For all other surfactant stock solutions, 300 mg of surfactant was dissolved in 30 mL of ultrapure water to form a 1% stock solution.

[0301] Nanonet formation determination:

[0302] The concentrated polymer (0.5% wt / vol stock solution) and surfactant (1% wt / vol surfactant) were mixed in a microcentrifuge tube. The amount of each stock solution used depended on the desired surfactant-to-polymer ratio in subsequent examples. The combined concentrated stock solutions in the microcentrifuge tube were then diluted with ultrapure water to a final volume of 1 mL. The tube was manually inverted three times to mix, allowed to stand for 5 minutes, and then 1 drop (approximately 10 μL) of 12 M hydrochloric acid was added to promote nanonetwork precipitation. The tube was inverted three times to mix, and allowed to stand for 5 minutes at room temperature. To detect nanonetwork formation, the absorbance of the tube contents was measured at 540 nm.

[0303] Size measurement using dynamic light scattering (DLS):

[0304] Using dynamic light scattering (Zetasizer Nano ZS) TM Polymer particle size, surfactant aggregate size, and nanonetwork size were measured. Briefly, a 0.5% wt / vol surfactant solution was prepared in buffer A (20 mM Tris-HCl {tris(hydroxymethyl)aminomethane}, pH 7). The surfactant was mixed with the specified polymer at a 1:1 ratio (wt / wt) and allowed to stand at room temperature for 5 minutes. Alternatively, samples of polymer only and surfactant only were mixed with equal volumes of buffer A and incubated for the same time period. After 5 minutes, large aggregates and dust were removed from the solution through a 0.2 μm filter, and the size was immediately measured by dynamic light scattering (absorbance at 540 nm). During sizing, the sample was diluted dropwise in buffer A to obtain the optimal polydispersity index (<0.5) for measurement. The value was used as a measure of the diameter of the surfactant aggregates, nanonetwork, and polymer particle diameter.

[0305] Flocculation rate experiment:

[0306] A 1% sodium oleate nanomesh was formed by adding a specified SMA polymer and sodium oleate in a 1:1 (wt:wt) ratio. The sodium oleate nanomesh solution was then diluted to 0.02 wt / volume% (in 1 mL of ultrapure water) and allowed to stand for 5 minutes at room temperature (21 °C) in a polystyrene cuvette. The nanomesh was subsequently destabilized by acidification (1 drop of 12 M HCl), and the absorbance was measured at 540 nm. The sedimentation of the precipitated sodium oleate nanomesh flocs was tracked over time. As a control, the sedimentation behavior of the acidified sodium oleate aggregates was also tracked over time.

[0307] Example 1

[0308] Size characterization of nonionic surfactant aggregates.

[0309] Using the same surfactant family, with a relatively small polymer (SMA-2000) TM ) and a relatively large polymer (SMA-725) TM A comparison of SMA polymers in nanonetwork formation. Each of these polymers is a styrene-maleic acid block copolymer. SMA-2000 TM and SMA-725 TM The average molecular weights are 6,000 Da and 130,000 Da, respectively.

[0310] To examine the relationship between polymer particle size and surfactant aggregate size during nanonetwork formation, Triton from the surfactant was tested. TM Surfactants from each of the X-series and polyglycerol-10-alkyl (PG) series. First, the average aggregate diameter of the surfactants was measured by dynamic light scattering (Table 2). For Triton... TM X-series surfactants, the higher the hydrophobic lipid balance (HLB) of the surfactant, the smaller the average aggregate diameter (D). TX-45 >D TX-305 ≈D TX-100 This may be due to the increase in the hydrophilic head group component of the surfactant, which can lead to an increase in the curvature of the surfactant aggregates, and thus a smaller measured diameter of the aggregates. For PG series surfactants, the measured aggregate diameter does not conform to this trend, which may be due to the varying length and saturation of the alkyl chain in the surfactant, which can alter monomer stacking and possible aggregate structure.

[0311]

[0312] Example 2

[0313] The self-assembly of nanonets can be driven by factors including the average particle size of the polymer, the average aggregate diameter of the surfactant, and the ratio of polymer to surfactant in the solution (wt / wt).

[0314] Here, the analysis of nanoweb formation begins by attempting to determine whether any given combination of surfactant and polymer leads to the co-precipitation of the surfactant and polymer into a complex upon solution acidification (Figure 2). PG and Triton TM Each of the surfactants in this series is generally stable in acidic solutions. However, it should be noted that the PG surfactant series can degrade slowly under very acidic conditions. In solutions combining a given SMA polymer and from PG or Triton... TM After a series of surfactant solutions are applied, even when polymer particles and surfactant aggregates interact, the overall negative charge dominates. This charge can be neutralized by protonation (by adding a proton source, such as an acid). Following this neutralization, a large amount of precipitate forms immediately and begins to flocculate and precipitate out of the solution. The formation of this precipitate can be measured by the change in absorbance of the solution at 540 nm, which is a measure of solution turbidity. The rate and amount of turbidity formation in any given solution will be used as a measure of nanoweb formation.

[0315] Triton X-100 TM Triton X-305 TMand Triton X-45 TM After the addition of the surfactant, co-precipitation of the surfactant and the polymer was observed. Figure 2A , 2B (and 2C, square). Once the surfactant-to-polymer ratio exceeds 1:1 (wt / wt), adding excess surfactant does not significantly increase precipitation. This indicates that once the polymer is saturated, excess surfactant will not be incorporated into the nanostructure composition.

[0316] In Triton X-305 TM In some cases, excessive surfactant (500 ppm) leads to the redissolution of the nano-mesh precipitate. Figure 2A (square). Using Triton X-100 TM A similar trend was observed, but much higher concentrations (>500 ppm) were required to induce the dissolution of the nano-mesh precipitate. Figure 2B (square). In Triton X-45 TM In this case, high concentrations of surfactant are turbid, which hinders the distinction between the nano-network precipitate and the basic surfactant aggregates, and therefore no redissolution was detected.

[0317] At a ratio of 1:1wt:wt, SMA-2000 TM The polymer is able to work with Triton TM Any of the series of surfactants forms a nanonetwork and is co-deposited ( Figure 2A , 2B (and 2C, square). For the next test of the effect of polymer length on nanonetwork formation, a higher molecular weight polymer SMA-725 was used. TM Repeat the experiment. (Compare with SMA-2000) TM In comparison, SMA-725 TM Only compatible with Triton X-45 TM The relatively large surfactant aggregates formed form nanonetworks. Figure 2A , 2B (and 2C, triangle).

[0318] These experiments were repeated using the same two SMA polymers but with PG series surfactants. In almost all cases, the PG series surfactants were able to co-precipitate with both polymers, indicating the formation of a nanonetwork. These results are consistent with the macroaggregate diameters of the PG surfactants recorded by dynamic light scattering (Table 2). The smallest surfactant aggregate diameter recorded was 46 nm for polyglycerol-10-monooleate (PGL1), almost larger than that measured by SMA-725. TM The average particle size of the resulting polymer particles (10.7 nm, Table 2) is 4 times larger.

[0319] Example 3

[0320] The relationship between the average particle size of the polymer and the average aggregate diameter of the surfactant is a significant factor driving the formation of nanonetworks.

[0321] To understand why polymer average particle size can relate to nanonetwork formation, the average particle size of polymer particles in buffer solutions was measured by dynamic light scattering (Table 2). Although each polymer is an extended chain with a straight length (nm) under alkaline conditions, this extended chain conformation may not exist under other solution conditions. For example, in buffer solutions with neutral pH, polymers will typically exhibit a dense particulate structure with a measurable and calculable average particle size.

[0322] For example, consider SMA-2000 in dynamic light scattering measurements. TM Despite SMA-2000 TM With a straightening length of 14 nm, the polymer forms dense particles with an average particle size of ≈4 nm (Table 2). For SMA-725... TM The polymer formed particles with an average particle size of ≈10nm, but a straight length of approximately 350nm (Table 2).

[0323] Furthermore, based on our dynamic light scattering results, we also observed that Triton X-100 TM and Triton X-305 TM All formed surfactant aggregates with an average aggregate diameter of less than 10 nm (Table 2). Conversely, Triton X-45... TM Aggregates with an average aggregate diameter of 90 nm were formed (Table 2). Although all three surfactants were compatible with SMA-2000... TM Forming a nanonetwork, but only Triton X-45 TM With SMA-725 TM Forming nanonets ( Figure 2C ,triangle).

[0324] Based on these results, if the average aggregate diameter of the surfactant is greater than the average particle size of the polymer, the polymer-surfactant combination will form a nanonetwork. Therefore, since each PG series surfactant forms aggregates with an average aggregate diameter exceeding 40 nm, SMA-725... TM and SMA-2000 TM All of them can interact with it and form a nano-network (Table 3).

[0325]

[0326]

[0327] Example 4

[0328] The effect of polymer length on nanonet size.

[0329] To measure the size of the nanowebs, we used dynamic light scattering. The nanowebs typically have a diameter smaller than the average aggregate diameter of the surfactant (Table 4). This indicates that the polymer can compact or partially dissociate the surfactant aggregates. However, in some cases, the addition of the polymer produces nanowebs with no change in diameter compared to the average aggregate diameter of the surfactant aggregates alone, or even nanowebs with larger diameters, particularly with PGL2 and Triton X-45. TM In the case of (Table 4). Interestingly, these two polymers typically form nanonetworks of different sizes with the same surfactant. Surfactants with small alkyl chains (PGL4 and PGL2, N...) CH2 =12) and SMA-2000 TM The formed nano-network ratio is similar to SMA-725 TM The resulting nanonetworks are 2 to 4 times smaller (Table 4). Surprisingly, however, when using surfactants with long alkyl chains (alkyl chain carbon > 12), the longer straightened length of SMA-725... TM Polymers typically form with properties greater than those derived from SMA-2000 TM The nanonetworks formed have smaller diameters (Table 2). Several smaller polymers (SMA-2000) stabilized the same surfactant aggregates. TM Compared to the higher entropy contribution of the surfactant aggregates, this smaller nanonetwork size is likely due to the individual long polymers (SMA-725) that stabilize the surfactant aggregates. TM The reduced free energy requirement.

[0330]

[0331] Example 5

[0332] This embodiment compares the average particle size of the polymer with the stability of the nanonetwork formed by the polymer while keeping the average aggregate diameter of the surfactant constant. The comparison is made using SMA-2000. TM and SMA-725 TM The flocculation efficiency (e.g., formation rate) of the formed sodium oleate nanonetwork ( Figure 3A Sodium oleate forms large surfactant aggregates with an average aggregate diameter of 392 nm (Table 2), thus interacting with SMA-2000. TM and SMA-725 TMSuitable for forming nanonetworks. Sodium oleate has long alkyl chains (N... CH2 =18). Free sodium oleate in the solution will precipitate, but hardly any flocculation or sedimentation will occur. Figure 3B However, in the presence of SMA-725 TM In the nanonet, after destabilization by changing the pH ( Figure 3C The interacting polymers precipitate and rapidly aggregate with sodium oleate. This aggregation occurs quickly, instructing the nanonetwork to destabilize. Figure 3C In contrast, the short-chain polymer SMA-2000 TM Sodium oleate-based nanonetworks are formed that cannot flocculate well. This is evident from the precipitated SMA-2000. TM Sodium oleate-based nanonets settle relatively slowly. Figure 3D The flocculation of destabilized nanonets was quantitatively measured by observing the sludge removal from the solution after polymer destabilization. Figure 3E Quantitative measurements of flocculation rate and mass confirmed qualitative observations, namely that the sodium oleate nanonets formed by longer polymers exhibited faster aggregation kinetics, thus facilitating physical removal when used for wastewater treatment. Figure 3E ).

[0333] Example 6

[0334] Nanomesh additive for capturing oil and suspended solids from produced water

[0335] In this embodiment, both return water and produced water samples are used with a nanomesh. The water samples used are from typical Bakken Formation oil extraction activities. The hydrocarbon content of the water samples is measured before and after exposure to the nanomesh. SMA-2000 will be used. TM and Triton X-100 TM Nanomesh was added to both the return water sample and the produced water sample. Solids in the resulting mixture were then removed by filtration. The hydrocarbon content of each filtrate recovered from the treated water sample was then measured again. The results are listed in Table 5 below.

[0336]

[0337]

[0338] Example 7

[0339] Optimization of Nanomesh for Selective Iron Remediation in Produced Water

[0340] (Nanonets as a platform for selective pollutant removal)

[0341] Several different surfactants were screened to identify suitable surfactants for the preparation of iron-selective nanowebs. Additionally, lipid SMA particles (lecithin) were determined. In the screening procedure, iron-selective nanowebs capable of selectively capturing iron from water produced by unconventional oil and gas operations were identified. Once the surfactants were identified, the nanoweb formulation could be further refined for easy removal by dissolved air flotation and / or filtration.

[0342] Sodium oleate, CAPB TM Each of (cocamidopropyl betaine), PGL1, PGL2, PGL3, PGL4, PGLW, and cocoyl glycinate is associated with polymer SMA-2000. TM A nanonetwork was formed at a surfactant:polymer ratio of 5:1 wt. The lipid-SMA formulations (lecithin and SMA-2000) were also tested. TM Nanomesh was added to solutions containing dissolved iron at three different concentrations of divalent cations (4000 ppm, 400 ppm, and 40 ppm). A first control without nanomesh and a second control with KOH were also tested. Two separate experiments were performed. In the first, the solution with nanomesh or SMA-lecithin was left to stand overnight and then filtered. In the second, the solution with nanomesh or SMA-lecithin was left to stand for 10 minutes and then filtered. The controls were also filtered after the required elapsed time.

[0343] Sodium oleate and polyglycerol-10 monostearate (PGL5) showed to trap iron into SMA-2000 TM The PGL5 (PGLW) surfactant exhibits good targeting properties within the nanomesh network. It shows the most consistent removal across the calcium concentration range. Conversely, when considering all tested surfactants as a whole, results tend to show relatively good removal at 400 ppm calcium and relatively poor removal at 4000 ppm calcium. PGL series surfactants are generally insensitive to calcium concentration. Surfactants with high binding affinity for iron (e.g., cocoyl glycinate) appear to be more negatively affected by calcium ion concentration. Figure 4 and Figure 5 The results are shown in charts.

[0344] Example 8

[0345] Fourteen (14) different nanonets were prepared. Each nanonet contained SMA-2000 TM Or SMA-725 TM And one of the following surfactants: sodium oleate, PGL2, PGL3, and cocoyl glycinate. SMA-lecithin formulations were also tested. Each nanomesh was then added to a solution containing different concentrations of Fe.2+ and Ca 2+ In various solutions containing ions. In the first experiment, the treated solution was left to stand for 10 minutes. In the second experiment, the treated solution was left to stand for 12 hours. The results showed that SMA-2000 TM Nanomesh is better than SMA-725 at removing iron. TM Nanomesh performed relatively better. Increasing the concentration of divalent cations such as calcium generally reduced the iron-binding capacity of the nanomesh. A control group without nanomesh and treated only with KOH was also tested. The results are graphically presented in Figure 6.

[0346] Example 9

[0347] Using SMA-725 TM Four (4) nanonetworks were prepared as polymers using one of the following surfactants: PGL2, PGLW, sodium oleate, and cocoyl glycinate. An SMA-lecithin control was also tested. A 75:25 Fe nanonetwork was prepared at a concentration of 100 ppm. 3+ :Fe 2+ The solutions contained iron ions. Then, one of each of the four nanomesh and SMA-lecithin formulations was added to a separate iron solution and allowed to stand for 10 minutes or 12 hours. A control group without nanomesh and treated only with KOH was also tested. The results, graphically shown in Figure 7, generally indicate that increasing the residence time of the iron solution treated with nanomesh generally increases the amount of iron removed.

[0348] Example 10

[0349] Six different nanowebs were prepared using sodium oleate as a surfactant and three different polymers. Each polymer was used to prepare two nanowebs; the first nanoweb contained a polymer:surfactant ratio of 1:5 wt, and the second nanoweb contained a polymer:surfactant ratio of 1:1 wt. Figure 8 The results are presented in a graph. This graph typically shows that increasing the surfactant concentration within the nanonet increases iron removal. This indicates that iron removal depends at least in part on the surfactant concentration within the nanonet, and not solely on the pH of the nanonet mixture.

[0350] Example 11

[0351] Preparation containing SMA-725 TMNanonetworks of one of the following surfactants: PGL5, cocoyl glycinate or sodium oleate, and SMA lecithin formulation, were added to separate produced water samples. The produced water contained 500 ppm oil, >100,000 ppm total dissolved solids (TDS), and >10,000 ppm divalent cations. A first control without a nanonetwork and a second control without a nanonetwork and treated only with KOH were also tested. Figure 9 and Figure 10 The results are shown in the figure. Generally, the results indicate that sodium oleate-based nanomesh provides a relatively better combination of oil and iron removal in actual produced water samples.

[0352] Example 12

[0353] Sodium oleate nanomesh can be modified to enhance flotation by adding a small amount of polyglycerol-10 monostearate (OPGW nanomesh).

[0354] Preparation containing SMA-725 TM OPGW nanomesh, containing 75% sodium oleate, 25% polyglycerol-10 monostearate, and a polymer:surfactant weight ratio of 1:1, was used. The nanomesh was then added to collected water samples with different levels of elevated divalent cations (10 ppm iron, 50 ppm iron, and 100 ppm iron) and allowed to stand for 10 minutes. The samples were then filtered, and the iron content of the filtrate from the treated water samples was tested. Figure 11A ),color( Figure 11B ) and turbidity ( Figure 11C The study also tested a first control without the addition of a nanomesh and a second control without a nanomesh and treated only with KOH. The results generally indicate that the OPGW nanomesh rapidly removes iron, oil, and gas from the produced water samples in the presence of elevated divalent cations.

[0355] Example 13

[0356] OPGW nanomesh enhances the removal of iron and hydrocarbons from produced water based on dissolved air flotation (DAF).

[0357] OPGW nanomesh was prepared as described above and added to the produced water sample, followed by dissolved air flotation (DAF) treatment and filtration. Iron content, color, and turbidity of the samples were tested again before and after adding the nanomesh and filtration. A control without nanomesh was also tested. The total iron concentration of the filtrate from the treated water sample was determined by the ferrazine method. The yellow color, indicating dissolved hydrocarbons and colloidal iron, was measured by absorbance at 350 nm. Turbidity was measured by absorbance at 540 nm. The results are graphically presented in Figure 12.

[0358] Example 14

[0359] Tested OPGW nanomesh (SMA-725) TM Iron concentration and extractable petroleum hydrocarbons were measured in produced water treated with 75% sodium oleate, 25% polyglycerol-10 monostearate (polymer:surfactant in a 1:1 weight ratio), a first control of untreated produced water, and a second control of produced water filtered only without a nanomesh. All samples were vigorously mixed for 10 minutes with air added. The results are shown in Figure 13.

[0360] In the following Examples 15 to 21, the following methods, reagents and materials were used.

[0361] Reagents and Materials Examples 15-21:

[0362] Poly(styrene-co-maleic anhydride) polymers were purchased from Jiaxing Huawen Chemical Co., Ltd. (SMA-725TM, lot number S190405A01) or Cray Valley™ (SMA-2021TM, lot number 204222A; SMA-2000TM, lot number PS16072901; and SMA-3000TM, lot number PS16111302). Polymers SMA-725TM and SMA-2021TM were ground into a fine powder before use. Poly(diisobutylene-alt-maleic acid) (DIBMATM, lot number 4217473) was purchased from Anatrace, while polymers poly(styrene-co-maleic anhydride), cumene-terminated (SMA-cumene-terminated, lot number 08728HN) and poly(styrene-co-maleic anhydride), partially isobutyl ester (SMA-IBE, lot number 09918JN) were purchased from Sigma Aldrich.

[0363] Nonionic surfactants 4-(1,1,3,3-tetramethylbutyl)phenyl-polyethylene glycol Triton™ X-100, lot number SLBX5574; Triton™ X-305 (70% in H2O), lot number SLBX0207; Triton™ X-45, lot number SLBX0207; CAS No. 9002-93-1), Span 20™ (CAS No. 1338-39-2, lot number MKCF5665), Tween 20™ (CAS No. 9005-64-5, lot number SLBW9887), Tween 20™ (CAS No. 9005-64-5, lot number SLBW9887), and Tween 20™ (CAS No. 9005-64-5, lot number SLBW9887) are mentioned. 40TM; CAS No. 9005-66-7, Lot No. MKBV6853V), polyethylene glycol dehydrated sorbitan monostearate (Tween 60TM; CAS No. 9005-67-8, Lot No. MKBX0810V), polyethylene oxide dehydrated sorbitan tristearate (Tween 65TM; CAS No. 9005-71-1, Lot No. MKCG4378), polyethylene glycol dehydrated sorbitan monooleate (Tween 80TM; CAS No. 9005-65-6, Lot No. BCBV5152), and polyethylene glycol dehydrated sorbitan trioleate (Tween... 85TM; CAS No. 9005-70-3, Lot No. MKCG2988), (Z)-9-octadecenoate sodium salt (sodium oleate TM; CAS No. 143-19-1, Lot No. SZBG1110V), p-toluenesulfinate sodium salt hydrate (p-toluenesulfinate sodium hydrate TM; CAS No. 207801-20-5, Lot No. MKCD1005), 1-octanesulfonate sodium salt monohydrate (1-octanesulfonate sodium monohydrate TM; CAS No. 207596-29-0, Lot No. BCBW1986), 9,10-dihydro- Sodium 9,10-dioxo-2-anthraquinone sulfonate monohydrate (anthraquinone-2-sulfonate sodium hydrate™; CAS No. 153277-35-1, lot No. MKCD1028), potassium o-ethyl xanthate (potassium ethyl xanthate™; CAS No. 140-89-6, lot No. 44706), sodium dodecylbenzene sulfonate (sodium dodecylbenzene sulfonate™; CAS No. 25155-30-0, lot No. STBH2778) and 1,2-hexanediol (CAS No. 6920-22-5, lot No. STBH6345) were purchased from Sigma Aldrich.

[0364] Poly(oxy-1,2-ethylene glycol)-α-isotridecyl-ω-hydroxyphosphate (Lakeland PAE 136TM, CAS No. 73038-25-2, Lot No. W475) was purchased from Lakeland Labs, Ltd. (Z)-9-octadecenoic acid (oleic acid™, CAS No. 112-80-0, Lot No. SJ1-111) was purchased from Vantage. Polyethylene glycol monoalkyl ether (Genapol X-080TM, CAS No. 9043-30-5) was purchased from Fluka, while lauramidopropyl betaine (TC-LAB 35TM, CAS No. 86438-78-0) and potassium cocoyl glycinate (Amin GCK 30HTM, CAS No. 301341-58-2) were purchased from Tinci. Sodium-1-dodecanesulfonate (sodium dodecane-1-sulfonate™, CAS No. 2386-53-0, lot No. K49293246 806) was purchased from Merck KGaA. Alkyl polyglucoside (coco-glucoside™, CAS No. 141464-42-8, lot No. 16072-A52) was purchased from New Directions. Decaglyceryl monostearate (polyglycerol-10-stearate™, CAS No. 79777-30-3), decaglyceryl monolaurate (polyglycerol-10-laurate™, CAS No. 34406-66-1), (polyglycerol-10-palmitate™), and triglyceryl monooleate (polyglycerol-10-oleate™, CAS No. 11094-60-3) were obtained from Shandong Binzhou GIN&ING New Material Technology Co., Ltd. Sodium benzenesulfonate (C 10-16 (Bio Soft D-40TM, CAS No. 68081-81-2, Batch No. 8252764), Sodium Olefin Sulfonate (C 14-16 (Bio Terge AS-40™, CAS No. 68439-57-6, Lot No. 8242348), Sodium lauryl sulfoacetate (Lathanol LAL Powder™, CAS No. 1847-58-1, Lot No. 8170061), Sodium lauroyl lactate (Stepan SLLFB™, CAS No. 13557-75-0, Lot No. 8086194), Lauryl lactate (Stepan Mild L3™, CAS No. 910661-93-7, Lot No. 8080185), Alkylbenzene sulfonic acid (C 11-13(Stepan Sulfonic 100™, CAS No. 68608-88-8, Lot No. TK-265), sodium tridecyl ether sulfate (Cedepal TD-403 MFLD™, CAS No. 25446-78-0, Lot No. 7606923), disodium coconut oil amphiphilic dipropionate (Amphosol 2CSF™, CAS No. 68604-71-7, Lot No. S77072810) and isopropylamine alkylbenzene sulfonic acid (C 9-17 (Br)(Ninate 411TM, CAS No. 68649-00-3, Lot No. 8082275) purchased from Stepan Company. VDISTILL DV53 TM Distilled soybean fatty acids (CAS No. 68308-53-2, Batch No. 829608) and VDISTILL DV 63 TMDistilled Canola fatty acids (lot number 833603) were purchased from Vantage. n-decyl-β-D-thiomaltodextrin (n-decyl-β-D-thiopyranomaltodextrin™, CAS No. 148565-56-4, lot number 4216901), 1H,1H,2H-perfluorooctyl-β-D-pyranomaltodextrin (fluorinated octyl maltodextrin™, CAS No. 118680-70-9, lot number 4217259), n-dodecyl-β-D-thiomaltodextrin (n-dodecyl-β-D-thiopyranomaltodextrin™, CAS No. 148565-58-6, lot number 4216186), 1,2,5,6-tetradecyl-β-D-glucopyranoside-3,4-O-di-dodecyl- D-Mannitol (perGlu-bis(dodecylmannitol)™, lot number 4217252; 1,2,5,6-tetradecyl-β-D-glucopyranoside-3,4-O-di-tetrayl-d-mannitol (perGlu-bis(tetraylmannitol)™, lot number 4217317); 1,2,5,6-tetradecyl-β-D-glucopyranoside-3,4-O-di-tetrayl-d-mannitol (pergGlu-bis(tetradecylmannitol)™, lot number 4217150); 3,6,9,12,15,18,21,24-octaoxahexadecane-1-ol (octaethylene glycol monododecyl ether™, CAS number 3) 055-98-9, batch number 4217388), n-decyl-β-D-thioglucoside (n-decyl-β-D-thioglucopyranoside™, CAS No. 98854-16-1, batch number 127098), n-nonyl-β-D-thioglucoside (n-nonyl-β-D-thioglucopyranoside™, CAS No. 98854-15-0, batch number 4216868), hexaethylene glycol monodecyl ether (decyl hexaethylene glycol ether™, CAS No. 5168-89-0, batch number 4157194), n-heptyl-β-D-thioglucoside (n-heptyl-β-D-thioglucopyranoside™, CAS No. 856) The following products were purchased from Anatrace: 18-20-8, lot number 4216927; n-octyl-β-D-thiomaltodextrin (n-octyl-β-D-thiopyranomaltodextrin™, CAS No. 148616-91-5, lot number 4216064); decyl hexaethylene glycol ether (hexaethylene glycol monooctyl ether™, CAS No. 4440-54-4, lot number 4216205); hexaethylene glycol monododecyl ether (dodecyl hexaethylene glycol ether, CAS No. 3055-96-7, lot number 4215962); and dodecyl heptaethylene glycol ether (heptaethylene glycol monododecyl ether™, CAS No. 3055-97-8, lot number 4216865).

[0365] N-Octayl-L-methionine (CAS No. 35440-75-6), n-decyl-L-methionine (CAS No. 51570-51-5), n-dodecanoyl-L-methionine (CAS No. 35440-74-5), n-octayl-L-threonine (CAS No. 91694-75-6), n-decyl-L-threonine (CAS No. 30664-76-7), n-dodecanoyl-L-threonine (CAS No. 14379-57-8), and n-dodecanoyl-L-histidine (CAS No. 55258-11-2) were synthesized by GreenCentre Canada.

[0366] The following abbreviations can be used for Anatrace surfactants: n-decyl-β-D-thiopyranoside is nDDTP-D335, fluorinated octyl maltoside is PFDMP-O310F, n-dodecyl-β-D-thiopyranoside is nDDDTP-D342, perGlu-bis(dodecyl)mannitol is DDDM-MNA-C12, perGlu-bis(tridecyl)mannitol is pGBTM-MNA-C13, pergGlu-bis(tetradecyl)mannitol is pGBTEM-MNA-C14, and octaethylene glycol monododecyl ether is OEGMDE- O330, n-decyl-β-D-thiopyranoglobin is nDDTGP-D323, n-nonyl-β-D-thiopyranoglobin is nNDTP-N335, hexaethylene glycol monooctyl ether is HEGMOE-H350, n-heptyl-β-D-thiopyranoglobin is nHDTP-H301, n-octyl-β-D-thiopyranomaltodextrin is nODTTP-O320, hexaethylene glycol monodecyl ether is HEGMDE-H360, hexaethylene glycol monododecyl ether is HEGMDDE-H370, and hexaethylene glycol monododecyl ether is HXEGMDDE-H375.

[0367] Polymer hydrolysis:

[0368] First, SMA-725 TM (Jiaxing Huawen Chemical Co. TM ) and SMA-2021 TM (CrayValley TM Grind into a fine powder, and SMA-2000 TM (Cray Valley TM SMA-3000 TM (Cray Valley TM ), DIBMA (Anatrace) TMSMA-cumene-terminated (Sigma Aldrich) TM ) and SMA-IBE (Sigma Aldrich TM Purchased in powder form.

[0369] Add 500 mM deionized water of potassium hydroxide (KOH) to a three-necked round-bottom flask connected to a condenser and heat to 50°C. Add 5% (wt / vol) SMA-X to the warm KOH solution. TM (X = SMA-725) TM SMA-2000 TM SMA-3000 TM SMA-2021 TM The polymer (cumene-terminated, IBE) was heated and refluxed at 100°C for 3 hours. During reflux, the polymer completely dissolved, which is beneficial for SMA-725. TM and SMA-2021 TM The reaction yielded a clear, yellow solution. The reaction mixture was cooled to ambient temperature and then filtered to remove unhydrolyzed particles. The filtrate was precipitated by adding 12M HCl dropwise with stirring until a pH ≤2 was reached. The precipitate was filtered using a 10μm filter, washed three times with 100mL of dilute 50mM HCl solution, and then three times with 100mL of deionized water. The separated colorless polymer was dried at ambient temperature for 2 hours and then lyophilized overnight, approximately 12 hours.

[0370] Preparation of derived SMA-2000 TM

[0371]

[0372] Option 1. SMA-2000 TM Reaction with ethanolamine.

[0373] In a reaction vessel equipped with a magnetic stir bar, 0.200 g of SMA-2000 was added. TM The powder was dissolved in 10 mL of dimethylformamide to give a clear yellow solution. 20 μL of triethylamine and 99 μL of ethanolamine were added to this reaction mixture. A color change from yellow to colorless was observed. The reaction mixture was stirred at room temperature for 24 hours. After adding 51 mL of acidic aqueous solution, a colorless suspension was obtained, and the supernatant was decanted. 2 mL of tetrahydrofuran was added to the colorless precipitate, and the precipitate was dissolved overnight and allowed to evaporate over two days. Yield: 0.234 g. FTIR (ATR, cm⁻¹) -1):3380,3027,2930,2887,1769,1717,1653,1596,1492,1452,1387,1176,1061,1033,916,760,699.

[0374] Infrared spectroscopy

[0375] Fourier transform infrared spectroscopy (FTIR) was performed on commercially available poly(styrene-co-maleic anhydride) and poly(styrene-co-maleic acid) polymers using an Agilent Technologies Cary 630 spectrometer. The spectrometer was equipped with a diamond ATR (attenuated total reflectance). The range was 400–4000 cm⁻¹. -1 Spectra were recorded within the range, with an average of 4 scans and a resolution of 1 cm. - 1. At 1775cm -1 and 1855cm -1 The vibrational stretching mode of maleic anhydride was observed at C=O at 1705 cm. -1 C=O maleic acid stretching mode was detected at the site (see Killian et al., Chemistry and Physics of Lipids (2019), 218, 85-90).

[0376] Preparation of 2% polymer stock solution:

[0377] 200 mg of anhydrous polymer was suspended in deionized water, and the pH was adjusted to 7-8 by adding 500 mM potassium hydroxide solution dropwise. The polymer solution was sonicated to obtain a homogeneous solution and adjusted to a final volume of 10 mL. The polymer solution was filtered using a 0.22 mm nylon filter.

[0378] Preparation of a 1% surfactant stock solution:

[0379] Dissolve 150 mg of each surfactant in 15 mL of deionized water to prepare a separate 1% stock solution for each surfactant. Dissolve the following surfactants—N-octanoyl-L-methionine, N-dodecanoyl-L-methionine, N-decanoyl-L-threonine, N-dodecanoyl-L-threonine, and N-dodecanoyl-L-histidine—in deionized water and adjust the pH to 8 to ensure complete dissolution of the surfactants. Filter the surfactant solutions using a 0.22 mm nylon filter.

[0380] Model surfactant Triton TM The chemical structures of the X series are shown in equation (i):

[0381]

[0382] Triton TM X-100, where n = 9-10; Triton TM X-305, where n = 30; Triton TM X-45, where n=5.

[0383] Particle size analysis of DLS:

[0384] Using Malvern Model ZEN1600 NanoSizer-S TM The instrument (Malvern Instruments Inc., Westborough, MA, USA) measures particle size with intensity values ​​using dynamic light scattering at a scattering angle of 173° at 25°C. The Malvern Zetasizer Nano ZS was used. TM The number intensity values ​​of hydrolyzed polymer and surfactant samples were obtained at 25°C and a scattering angle of 173°.

[0385] Surfactant solutions and hydrolyzed polymer solutions were prepared at ambient temperature in a 20 mM Tris-HCl {tris(hydroxymethyl)aminomethane} pH 7 buffer and diluted to concentrations from 1% to 0.1% in Tris-HCl buffer. Samples were filtered using 0.22 μM or 0.45 μM nylon filters and then immediately subjected to sizing analysis in disposable cuvettes. The solutions were diluted to obtain the optimal dispersibility index (<0.5) for measuring surfactant aggregate diameter and polymer particle size. Surfactant nDDTGP-D323 was prepared in 20 mM Tris pH 7 and methanol (1:1 ratio). In one example, the intensity value was considered as either surfactant aggregate diameter or polymer particle size. In another example, the numerical value was considered as either surfactant aggregate diameter or polymer particle size.

[0386]

[0387]

[0388]

[0389]

[0390]

[0391]

[0392]

[0393]

[0394]

[0395]

[0396]

[0397]

[0398]

[0399]

[0400]

[0401] Gel permeation chromatography (GPC)

[0402] Polymer molecular weight distribution analysis of a commercially available poly(styrene-co-maleic anhydride) polymer was performed by gel permeation chromatography (GPC) on a Viscotek GPCmax Ve-2001 using a routinely calibrated 2 mg / mL polystyrene standard with tetrahydrofuran (THF) as eluent at a rate of 1 mL / min. Samples were filtered using a 0.22 μm nylon filter prior to injection. Measurements were performed by GreenCentre Canada.

[0403]

[0404] Nanonet Formation Experiment - Method #1

[0405] Add 200 ppm of a 2% polymer stock solution to each well of a 96-well plate, followed by a 1% surfactant stock solution selected from six concentrations (1000 ppm, 500 ppm, 250 ppm, 125 ppm, 50 ppm, and 0 ppm). Dilute the polymer and surfactant mixture in deionized water to a final volume of 200 mL in each well. Add 10 mL of 12M hydrochloric acid (HCl) to the mixture as a precipitant. Observe nanoweb formation based on the turbidity of the mixture in each well. The degree of turbidity (an indicator of nanoweb formation) is determined by absorbance measurement at 540 nm on a Molecular Devices-SPECTRAmax M2. Each surfactant and polymer combination is performed in triplicate.

[0406] Nanonet Formation Efficiency - Method #2

[0407] Method #2 describes the use of Triton TM X's surfactant (Triton) TMX-100, Triton TM X-305 and Triton TM X-45) and polymers containing SMA (SMA-725) TM SMA-2000 TM SMA-2021 TM SMA-3000 TM The nanonetwork composite efficiency was determined. The aim was to determine the surfactant loading capacity of the polymer and to investigate the effect of polymer length. For the range of surfactant concentrations used, a ratio of two times the nanonetwork forming factor (Nf) of each selected surfactant and polymer was employed. A total of six concentrations were selected. The nanonetwork forming factor (Nf) was calculated using method #4 and is described below. For each titration, the polymer concentration was 400 ppm (20 μL).

[0408] Nanomesh titration:

[0409] Titrations of surfactants and polymers at given concentrations (see below) were performed using 1.5 mL centrifuge tubes, followed by dilution to a final volume of 1.0 mL in deionized water. The resulting nanonets were obtained by adding 10 μL of 12 M HCl. Titrations were performed in triplicate. Separate controls were prepared, one containing surfactant in deionized water and the other containing a mixture of surfactant and HCl. A portion (approximately 200 μL) of the prepared nanonets, the surfactant control, and the surfactant control with HCl were transferred to 96-well plates, and absorbance was measured at 540 nm. The prepared nanonets, surfactant controls with and without acid were analyzed using Sigma-Aldrich. TM 4-16 Centrifuge at 2300 rpm (816 rcf) for 10 minutes. Transfer the supernatant (approximately 200 μL) to a 96-well UV plate and measure the absorbance at 280 nm. Record the average absorbance value.

[0410] These are the surfactant and polymer concentrations used: SMA-2000 TM (400ppm, 20μL), Triton TM X-100(1000,500,250,100,64.8,0ppm); SMA-725 TM (400ppm, 20μL), Triton TM X-100(1000,500,295.16,250,100,0ppm); SMA-3000 TM (400ppm, 20μL), Triton TMX-100(1000,500,250,100,13.4,0ppm);SMA-2021 TM (400ppm,20μL),Triton TM X-100(1000,500,250,91.22,0ppm)。

[0411] SMA-2000 TM (400ppm,20μL),Triton TM X-305(1000,500,250,231.58,100,0ppm);SMA-725 TM (400ppm,20μL),Triton TM X-305(1000,500,473.76,250,100,0ppm);SMA-3000 TM (400ppm,20μL),Triton TM X-305(1000,500,447.88,250,100,0ppm);SMA-2021 TM (400ppm,20μL),Triton TM X-305(1000,500,436.88,250,100,0ppm)。

[0412] SMA-2000 TM (400ppm,20μL),Triton TM X-45(1000,616.18,500,250,100,0ppm);SMA-725 TM (400ppm,20μL),Triton TM X-45(1000,500,250,100,92.92,0ppm);SMA-3000 TM (400ppm,20μL),Triton TM X-45(1000,500,250,99.7,0ppm);SMA-2021 TM (400ppm,20μL),Triton TM X-305(1000,500,250,158.4,100,0ppm)。

[0413] Removing Zn from seawater 2+ and Cu 2+ Metal Ions – Method #3

[0414] A deionized aqueous solution of surfactant and hydrolyzed polymer was mixed into a 96-well plate to obtain a total of 1 mL of 0.5% nanonet library stock solution. 199 different nanonets were prepared. Each well of the 96-well plate contained a unique 1 mL nanonet solution.

[0415] Zinc and copper concentrations were determined colorimetrically using zinc reagent.

[0416] As proof of the principle of the optimized nanonet library, 10 ppm of zinc or copper was added to seawater and treated with a nanonet. The treatment procedure is as follows. To prepare the seawater solution with added metal, 175 μL of 100 nM Zn was added. 2+ Solution (28,765 ppm Zn) 2+ ) or 315 μL of 100 nM Cu 2+ The solution was added to 500 mL of seawater, yielding 10.07 ppm Zn. 2+ and 10.03 ppm Cu 2+ Solution. Then, 960 μL volumes of this sample were treated with 40 μL of each optimized nanomesh library solution (Tables 9 and 10). As a positive control for metal removal, a separate 960 μL aliquot of the metal-doped seawater sample was treated with 40 μL of 1% NaOH solution to precipitate Zn or Cu as hydroxide. To ensure metal stability in seawater, another 960 μL aliquot of the metal-doped seawater solution was mixed with 40 μL of distilled water. The solutions were mixed separately and centrifuged (1,000 x g) for approximately 5 minutes each to allow the precipitated nanomesh to settle. Application for Zn 2+ and Cu 2+ A method for removing metal ions was used to analyze 5 μL of the supernatant.

[0417] Preparation of calibration curves for method #3

[0418] Preparation of calibration standards

[0419] To dissolve Zn 2+ Metal ions were used as calibration standards, prepared at concentrations of 0.10, 0.26, 0.52, 1.03, 1.75, and 2.52 ppm, and for the dissolution of Cu... 2+ The calibration standards were prepared at concentrations of 0.10, 0.25, 0.5, 1.0, 1.74, and 2.49 ppm.

[0420] Zn used for dissolution 2+ and Cu 2+ Preparation of calibration dashed lines

[0421] Add 25 μL of Zn to a set of 1.5 mL conical centrifuge tubes. 2+ Aliquots of the calibration standard solution. Add 25 μL of Cu to another set of 1.5 mL conical centrifuge tubes. 2+Aliquots of the calibration standard solution were prepared. 950 μL of borate buffer (pH 9) was added to both sets of tubes, and the tubes were mixed. Then, 25 μL of 1.6 M zinc reagent solution (75% dye content) was added. The mixture was dissolved and allowed to stand for 5 minutes. Aliquots of 200 μL each were transferred to a 96-well flat-bottom plate suitable for visible spectrophotometry and the samples were measured at 615 nm. Zn was then prepared. 2+ and Cu 2+ A separate calibration curve.

[0422] Preparation of calibration curves for iron removal

[0423] The following procedure is based on MJ Verschoor, LA Molot, Limnol. Oceanogr-Meth., (2013), 11, 113-125. A Comparison of Three Colorimetric Methods of Ferrous and Total Reactive Iron Measurement in Freshwaters. (doi:10.4319 / lom.2013.11.113). The procedure was modified to quantify total and dissolved iron in water samples. 20,000 ppm Fe was prepared in water. 2+ A solution of 10% ascorbic acid and 2.5 mg / mL ferrazine. Add 20,000 ppm Fe... 2+ The solution was diluted to an appropriate concentration to prepare calibration standards. Fe was used at a concentration of 0.1–2.0 ppm in deionized water. 2+ The prepared calibration curve quantifies Fe 2+ and Fe 3+ .

[0424] Preparation of calibration standards

[0425] By continuously diluting 20,000 ppm Fe with deionized water 2+ Stock solutions were used to prepare calibration standards at concentrations of 0.10, 0.25, 0.50, 1.0, and 2.50 ppm.

[0426] Preparation of calibration curves

[0427] Add 1 mL of Fe to a 1.5 mL conical centrifuge tube. 2+ Add calibration standards and 100 μL of 10% ascorbic acid. Mix and allow to stand for 10 minutes. Add 25 μL of 2.5 mg / mL ferrazine solution and allow the sample to stand for 10 minutes. Transfer 200 μL aliquots of the sample to a 96-well plate suitable for visible spectrophotometry and analyze at 562 nm.

[0428] The same method was used to measure the total iron and dissolved iron concentrations.

[0429] The residual Zn was analyzed by complexation colorimetric determination using zinc reagent. 2+ and Cu 2+ Concentration. The zinc reagent method is adapted from the procedure described below (E). JMNeureuther, S. Siemann. Anal. Biochem., (2010), 397, 2, 218-226, (doi:10.1016 / j.ab.2009.10.037). A Spectrophotometric Method for the Determination of Zinc, Copper, and Cobalt ions in metalloproteins using ZinconCrystal). The procedure disclosed therein was modified and adapted to quantify dissolved Zn in water samples. 2+ and Cu 2+ Metal ions.

[0430] Theoretical Calculation - Method #4:

[0431] Seven hydrolyzed polymers and 58 surfactants at various concentrations were co-precipitated to produce nanomesh with varying turbidity. Turbidity was measured, and the rise in absorbance was simulated when surfactants were added to the polymers. First baseline absorbance values ​​αp and αs were calculated, estimated as a linear function of the concentration of a given polymer or surfactant when measured individually. The baseline-corrected absorbance value (A') was then calculated by subtracting αp and αs from the original absorbance value A, i.e., A' = A - αs - αp.

[0432] For each combination of polymer and surfactant, a curve A'(S,P0) is constructed, where S is the concentration of the surfactant and P0 is the fixed concentration of the polymer. The peaks of this curve are identified, and an sigmoid shape is fitted to the peak-front portion of the curve (R,optim function). The estimated sigmoid coefficients allow for quantification of peak height, transition midpoint, and transition rate.

[0433] For a given combination of surfactant and polymer, nanoweb formation was defined as any S-shaped fit with a height greater than 0.2. Furthermore, any S-shape with a midpoint exceeding 500 ppm was removed because the titration ended at 1000 ppm, and an S-shaped curve required at least three data points to be considered valid. Visual inspection confirmed that the S-shaped fit of A' was a useful method for detecting nanoweb formation. In total, 199 optimized nanowebs were detected out of 434 possible surfactant and polymer combinations (62*7).

[0434] Synthesis of surfactants

[0435] Nuclear magnetic resonance (NMR) spectroscopy was performed at the GreenCentre Canada facility. 1 H and 13 C{ 1 H NMR spectroscopy at room temperature in Varian TM Recorded on a 400 MHz spectrometer. Chemical shifts were reported in parts per million (ppm) using tetramethylsilane (TMS) as a standard. 1 H(CDCl3:7.26ppm; DMSO-d6:2.50ppm] and 13 C [CDCl3: 77.16 ppm; DMSO-d6: 39.52 ppm]. The chemical shift multiplets are reported as follows: s = singlet, d = doublet, dd = doublett, t = triplet, m = multiplet, and br = broad peak. NMR spectra were processed using MestReNova software. The spectra were prepared with a diamond ATR (attenuated total reflectance) and a wavelength range of 650–4000 cm⁻¹. -1 Fourier transform infrared (FTIR) spectra were recorded on an Agilent Cary 630 FTIR spectrometer with a ZnSe window covering the spectral range. The synthetic route of N-dodecanoyl-L-methionine can be found in (3) G. Bonacucina et al., Colloids and Surfaces A: Physicochem. Eng. Aspects, 2016, 492, 38-46. Chemical-Physical Properties and Cytotoxicity of N-Decanoyl Amino Acid-Based Surfactants: Effect of Polar Heads.

[0436] Synthesis of N-dodecanoyl-L-methionine

[0437] Methionine (1.50 g, 10 mmol), H₂O (20 mL), and Na₂CO₃ (1.57 g, 15 mmol) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar. THF (10 mL) was added, and the mixture became turbid. n-Dodecanoyl chloride (3.0 mL, 13 mmol) was added dropwise, and the mixture was stirred at room temperature for 4 h. After the specified time, the THF was evaporated under reduced pressure, and the reaction mixture was acidified to pH 2.0 (with 2N HCl). A precipitate formed and was filtered using a Buchner funnel with #2 filter paper, and washed with water (3 × 10 mL) and acetone (approximately 5–10 mL). The solid was dried overnight in a vacuum oven at 40 °C. The solid was recrystallized from hexane. The precipitate was then filtered and washed with hexane (3 × 10 mL) to give a pure product as a white solid (1.786 g, 54% yield). 1 H NMR(400MHz, CDCl3) δ6.83(d,J=7.6Hz,1H,NHCO),4.57(dd,J=12.4,4.8Hz,1H),2.54(t,J=7.6Hz,2H),2.23(t,J=7.6Hz ,2H),2.19–2.13(m,1H),2.09(s,3H),2.04–1.95(m,1H),1.63–1.56(m,2H),1.31–1.25(m,15H),0.87(t,J=6.8Hz,3H). 13 C NMR (100MHz, CDCl3) δ175.7(COOH),174.7(CONH),52.3(HC–NH),36.6(O=C–CH2),32.0(O=C–CH2–CH2),31.2(CH2),30.3(CH2),29. 8(CH2),29.7(CH2),29.7(CH2),29.5(CH2),29.5(CH2),29.4(CH2),25.8(CH2),22.8(CH2),15.6(SCH2),14.3(CH3); FT-IR(ATR,cm -1 ):3303,2938,2916,2849,1702,1706,1646,1535,1419,1226,685.

[0438] Synthesis of N-decanoyl-L-methionine

[0439] Methionine (1.50 g, 10 mmol), H₂O (20 mL), and Na₂CO₃ (1.6 g, 15 mmol) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar. After adding THF (10 mL) to the reaction mixture, a turbid solution formed. N-decanoyl chloride (2.7 mL, 13 mmol) was added dropwise, and the mixture was stirred at room temperature for 4 h. The solvent THF was evaporated under reduced pressure, and the reaction mixture was acidified to pH 2.0 (with 2N HCl). At pH 3–4, some precipitate formed an oil on top of the reaction mixture, observed at pH 2. The reaction mixture was extracted with hexane (30 mL) and EtOAc (ethyl acetate) (2 x 20 mL). The organic phases were combined, and the solvent was removed under reduced pressure. The oil was separated and stored in a refrigerator until a solid was obtained. The solid was recrystallized in hexane, filtered, and washed with hexane (3 x 10 mL) to give a pure colorless solid (2.516 g, 83% yield). 1 H NMR (400MHz, CDCl3) δ10.18(br,1H),6.55(d,J=7.6Hz,1H,NHCO),4.71(dd,J=12.8,5.6Hz,1H),2.55(t,J=7.4Hz,2H ),2.36–2.17(m,3H),2.10(s,3H),2.08–1.99(m,1H),1.68–1.58(m,2H),1.28–1.25(m,12H),0.87(t,J=6.8Hz,3H). 13 C NMR (100MHz, CDCl3) δ175.1(COOH),174.7(CONH),51.9(HC–NH),36.6(O=C–CH2),32.0(O=C–CH2–CH2),31.2(CH2),30.1(CH2 ),29.6(CH2),29.4(CH2),29.4(CH2),29.3(CH2),29.3(CH2),25.8(CH2),22.8(CH2),15.5(SCH2),14.2(CH3); FT-IR(ATR,cm -1 ):3314,2916,2849,1706,1650,1535,1441,1419,1255,1229,920,685.

[0440] Synthesis of N-octanoyl-L-methionine

[0441] Methionine (1.50 g, 10 mmol), H₂O (20 mL), and Na₂CO₃ (1.6 g, 15 mmol) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar. After adding THF (10 mL) to the reaction mixture, a turbid solution formed. n-Octanyl chloride (2.2 mL, 13 mmol) was added dropwise, and the mixture was stirred at ambient temperature for 4 h. The solvent THF was evaporated under reduced pressure on a Srankie line, and the reaction mixture was acidified to pH 2.0 (with 2N HCl). An oil formed on top of the reaction mixture. The reaction mixture was extracted with EtOAc (3 × 20 mL). The organic phases were combined, and the solvent was removed under reduced pressure. The oil was obtained and stored in a refrigerator to solidify. The solid was recrystallized in hexane, filtered, and washed with hexane (3 × 10 mL) to give a pure colorless solid (1.194 g, 43% yield). 1 H NMR (400MHz, CDCl3) δ10.54(br,1H),6.58(d,J=7.6Hz,1H,NHCO),4.70(dd,J=12.6,5.0Hz,1H),2.54(t,J=7.4Hz,2H),2.25(t, J=7.6Hz,2H),2.21–2.17(m,1H),2.09(s,3H),2.08–2.00(m,1H),1.63–1.60(m,2H),1.28–1.25(m,8H),0.86(t,J=6.6Hz,3H). 13 CNMR(100MHz, CDCl3)δ175.0(COOH),174.7(CONH),51.9(HC–NH),36.5(O=C–CH2),31.8(O=C–CH2–CH2),31 .2(CH2),30.1(CH2),29.2(CH2),29.1(CH2),25.7(CH2),22.7(CH2),15.5(SCH2),14.2(CH3); FTIR(ATR,cm -1 ):3329,2942,2919,2856,1698,1612,1549,1445,1248,1225,1188,1128,957.

[0442] Synthesis of N-dodecanoyl-L-histidine

[0443] Histidine (1.55 g, 10 mmol), H₂O (20 mL), and Na₂CO₃ (1.38 g, 13 mmol) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar, followed by the addition of THF (10 mL). The reaction mixture was cooled to 0 °C, at which point it became turbid. N-Dodecanoyl chloride (2.5 mL, 11 mmol) was added dropwise, and the mixture was stirred overnight at ambient temperature. Before the complete addition of the acyl chloride, the solution became turbid and viscous (gel-like). After reacting for 4 hours, the solvent THF was evaporated under reduced pressure, and the reaction mixture was acidified to pH 2.0 (with 2N HCl). The precipitate was filtered and washed with acetone (3 x 5 mL) and CHCl₃ (3 x 5 mL). The crude product... 1 ¹H NMR spectroscopy revealed residual dodecanoic acid, and the crude product was recrystallized in 95% EtOH. The solid was filtered and washed with 95% EtOH. The resulting colorless solid was contaminated with approximately 12% dodecanoic acid (1.197 g, approximately 35% yield). 1 H NMR (400MHz, DMSO-d6): δ8.01(d,J=7.6Hz,1H,NHCO),7.54(s,1H,N=CHN),6.78(s,1H,NCH=),4.41-4.35(m,1H,NCHCOOH),2 .94-2.77(m,2H,CH2),2.05(t,J=7.4Hz,2H,COCH2),1.41-1.38(m,2H),1.27-1.20(m,16H,CH2),0.85(t,J=6.8Hz,3H,CH3). 13 C NMR (100MHz, DMSO-d6): δ173.3(COOH), 172.1(CONH), 134.7(NC=N), 52.1(HC–NH), 35.2(O=C–CH2), 31.4(O=C–CH2–CH2), 29.1(CH2),29.1(CH2),29.0(CH2),28.9(CH2),28.8(CH2),28.6(CH2),25.2(CH2),22.1(CH2),14.0(CH3); FTIR(ATR,cm -1 ):3329,3146,2945,2919,2852,1639,1546,1397,1184,983,834,685.

[0444] Synthesis of N-dodecanoyl-L-threonine

[0445] Threonine (1.20 g, 10 mmol), H₂O (20 mL), and Na₂CO₃ (1.60 g, 15 mmol) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar. Then, THF (10 mL) was added, and the mixture became turbid. N-dodecanoyl chloride (3.0 mL, 13 mmol) was added dropwise, and the mixture was stirred at ambient temperature for 4 h. The solvent THF was evaporated under reduced pressure, and the reaction mixture was acidified to pH 2.0 (with 2N HCl). The colorless precipitate was filtered and washed with deionized water (3 × 10 mL), and dried in a vacuum oven at 40 °C for 3 days. The colorless solid (1.10 g, 36%) was purified by recrystallization from hexane. 1 H NMR (400MHz, DMSO-d6): δ7.75 (d, J=8.8Hz, 1H, NHCO), 4.20 (dd, J=8.8, 3.2Hz, 1H, CH–NH), 4.13-4.07 (m, 1H, CH–OH), 2.26-2. 11(m,2H,O=C–CH2),1.49-1.46(m,2H,CH2),1.23(m,15H,CH2),1.04(d,J=6.4Hz,3H,CHOH–CH3),0.85(t,J=6.8Hz,3H,CH3); 13 C NMR (100MHz, DMSO-d6): δ172.7(COOH),172.4(CONH),66.5(HC–OH),57.4(HC–NH),35.1(O=C–CH2),32.0(O=C–CH2–CH2),29 .1(CH2),29.0(CH2),28.9(CH2),28.8(CH2),28.7(CH2),25.4(CH2),22.5(CH2),20.5(HOHC–CH3),14.1(CH3); FTIR(ATR,cm -1 ):3426,3362,3314,2942,2919,2852,1709,1612,1605,1538,1463,1385,1382,1207,1151,1088,871,674.

[0446] Synthesis of N-decanoyl-L-threonine

[0447] Threonine (1.20 g, 10 mmol), H₂O (20 mL), and NaOH (0.6 g, 15 mmol) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar. Then, THF (10 mL) was added, followed by dropwise addition of n-decanoyl chloride (2.7 mL, 13 mmol), and the mixture was stirred overnight at ambient temperature. A suspension was obtained, and the solvent THF was evaporated under reduced pressure, and the reaction mixture was acidified to pH 2 (with 2N HCl). No precipitate was observed. The reaction mixture was extracted with EtOAc (3 × 20 mL). The organic phases were combined and the solvent was removed under reduced pressure. An oily substance was obtained and purified using a silica short-stopper, eluted with hexane / EtOAc 6:4 to remove decanoic acid, followed by elution with EtOAc to remove the product, resulting in a colorless solid (1.326 g, 49% yield). 1 H NMR (400MHz, CDCl3): δ7.00 (d, J=8.8Hz, 1H, NHCO), 4.54 (d, J=6.4Hz, 1H, CH–NH), 4.43-4.41 (m, 1H, CH–OH), 2.29 (t, J=7.6Hz ,2H,O=C–CH2),1.64-1.60(m,2H,CH2),1.28-1.25(m,15H,CH2),1.20(d,J=6.4Hz,3H,CHOH–CH3),0.87(t,J=6.6Hz,3H,CH3); 13 C NMR (100MHz, CDCl3): δ175.5 (COOH), 174.3 (CONH), 67.7 (HC–OH), 57.8 (HC–NH), 36.5 (O=C–CH2), 32.0 (O=C–CH2–CH2), 32.0 (CH2), 29. 7(CH2),29.7(CH2),29.6(CH2),29.5(CH2),29.4(CH2),29.4(CH2),25.9(CH2),22.8(CH2),19.6(HOHC–CH3),14.2(CH3); FTIR(ATR,cm -1 ):3426,3363,3314,2938,2919,2852,1709,1616,1605,1538,1419,1382,1277,1270,1199,1151,1087,875,675.

[0448] Synthesis of N-octanoyl-L-threonine

[0449] Threonine (1.20 g, 10 mmol), H₂O (20 mL), and Na₂CO₃ (1.60 g, 15 mmol) were added to a 100 mL round-bottom flask equipped with a magnetic stir bar. Then THF (10 mL) was added, followed by dropwise addition of n-octanoyl chloride (2.2 mL, 13 mmol). The reaction mixture was stirred at ambient temperature for 4 hours. After the specified time, the THF was evaporated under reduced pressure, and the reaction mixture was acidified to pH 2.0 (with 2N HCl). No precipitate was observed. The reaction mixture was extracted with 3x EtOAc (20 mL each time). The organic phases were combined and the solvent was removed under reduced pressure to give an oil. The oil was purified using a silica short-stopper, eluted with hexane / EtOAc 6:4 to remove decanoic acid, and then eluted with EtOAc to remove the product (1.039 g, 42% yield). 1 H NMR (400MHz, CDCl3): δ7.01 (d, J=8.4Hz, 1H, NHCO), 4.54 (dd, J=8.4, 2.4Hz, 1H, CH–NH), 4.42-4.40 (m, 1H, CH–OH), 2.29 (t, J=7.6 Hz,2H,O=C–CH2),1.63-1.60(m,2H,CH2),1.30-1.25(m,10H,CH2),1.19(d,J=6.0Hz,3H,CHOH–CH3),0.86(t,J=6.8Hz,3H,CH3); 13 C NMR (100MHz, CDCl3): δ176.3(COOH),173.7(CONH),67.7(HC–OH),57.5(HC–NH),36.4(O=C–CH2),3 2.5(O=C–CH2–CH2),29.1(CH2),25.8(CH2),22.7(CH2),19.4(HOHC–CH3),14.0(CH3); FTIR(ATR,cm -1 ):3303,2942,2927,2856,1724,1631,1534,1419,1415,1382,1210,1117,1084,1080,857,674.

[0450] Example 15

[0451] Nanonet formation

[0452] To rapidly screen for nanonetwork formation using any specific surfactant and polymer combination, a titration-based method is employed. An increasing amount of surfactant is added to a fixed amount of polymer. The polymer is then destabilized by the addition of concentrated hydrochloric acid, resulting in precipitation of both the surfactant and polymer, indicating nanonetwork formation. The amount of nanonetwork formation is measured by the increase in absorbance at 540 nm relative to a control of polymer-only and surfactant-only. This method can be used as a rapid, automated method for screening polymer-surfactant interactions, with the aim of observing the onset of nanonetwork formation in any given polymer and surfactant combination (see Reagents and Materials Examples 15-21, Method #1).

[0453] Using Triton TM Verification of a series of surfactants forming nanonetworks and screening methods.

[0454] To test the formation of nanonetworks using various surfactants and polymers, a screening method was designed using the co-precipitation of surfactants and polymers as a measure of nanonetwork formation. To test the screening method, samples from Triton were first measured. TM A series of model surfactants formed nanonetworks between styrene-maleic acid block copolymers of different lengths and block compositions (Figure 15). TM The series of surfactants corresponds to amphiphilic molecules with a hydrophobic alkyl chain of 14 carbons and a hydrophilic head group consisting of repeating oxyvinyl groups (see Formula (i) above). By increasing the number of repeating oxyvinyl groups, the HLB value of the surfactant increases and the size of the resulting surfactant aggregates decreases. This trend allows for the production of surfactants with similar chemical properties but fundamentally different physical wetting, foaming, and aggregation properties (Stubicar and Petres, Micelle Formation by Tritons in Aqueous Solutions, (1981), Croatia Chemica Acta, 54(3) 255-266).

[0455] Using SMA polymer and Triton TM A series of surfactants can validate screening methods for initiating nanoweb formation. The following is a Triton study using relatively small and relatively large SMA polymer particle sizes and relatively small and relatively large surfactant aggregate sizes. TM A comparison of nanonetwork formation of a series of surfactants. Therefore, many possible combinations of relative sizes can be observed. Triton was used. TM The surfactants are as follows (along with measured surfactant aggregate sizes): (Triton X-45) TM(156nm), and the surfactant that forms small micelles (Triton X-100) TM (10 nm). The polymer particle size and results are described in detail below.

[0456] Using Triton X-100 TM and SMA-2000 TM (D 计算值 2.6nm, D 观察值 (5.2nm) and SMA-3000 TM (D 计算值 2.8nm, D 观察值 A significant increase in absorbance was observed at 3.7 nm, indicating the formation of a nanomesh (Figure 15). Conversely, the relatively larger SMA-725... TM (D 计算值 6.8nm, D 观察值 (10-15nm) and Triton X-100 TM The absorbance showed almost no increase. All three polymers were made with Triton X-45. TM The larger surfactant aggregates that formed all showed a strong increase in absorbance. To confirm that this increase in absorbance corresponded to the formation of nanonetworks (and not just precipitation of a given component), the precipitates were removed from the solution by centrifugation. This was achieved using Triton X-rays for SMA 2000 and SMA 725. TM The UV absorbance of the surfactant was measured to determine the residual surfactant remaining in the solution (Table 21). The results showed that the increase in precipitate formation was proportional to the corresponding decrease in surfactant concentration in the supernatant. This result confirms coprecipitation as an effective screening method for measuring nanoweb formation (see Table 21). Reagents and Materials Examples 15-21, Method #2 The results obtained from the screening method confirm the claim that nanonetwork formation is affected by the size mismatch between the minimum polymer particle size and the surfactant aggregate size. For example, this claim can be stated as follows: (D 聚合物 <D 表面活性剂聚集体 =Nano mesh), and can be observed using the relatively simple, fast, and automated screening method detailed above. The results are shown in Figure 15.

[0457] Example 16

[0458] The transformation of nanomesh screening methods into high-throughput methods and the measurement of nanomesh formation.

[0459] To better measure nanonetwork formation between various surfactants and multiple polymers, a relatively more automated and quantitative scoring method for detecting nanonetwork formation has been developed. First, the simple screening method described above is considered and validated. In this validation, nanonetwork formation is assumed to occur between monoblock copolymers and monosurfactant aggregates. The following is a description of the computer-aided model developed to predict, normalize, and score nanonetwork formation.

[0460] After correcting for products containing only surfactants, the combined XY curve of absorbance at 540 nm versus surfactant concentration was fitted with an sigmoid function. Figure 16 The nanonetwork formation factor (Nf) is determined based on an S-shaped fit. Nf is taken from the half-maximum of the S-shape obtained from the S-shape fit. Nf can also be referred to as the midpoint, half-maximum concentration, or critical aggregation concentration. The S-shape fit also provides the values ​​of the absolute height and slope of the S-shape curve.

[0461] A steeper sigmoid curve can be produced by rapid association of all available surfactants with the polymer. This has been described as a sign of relatively high synergy in polymer-surfactant binding (Goddard EDPolymer / Surfactant Interaction - Its relevance to Detergent Systems. JAOCS. Vol 71, 1994). Similarly, a sigmoid curve with a relatively high maximum absorbance can indicate more association of available surfactants with the polymer and can also indicate more efficient nanoweb formation. Based on these two sigmoid curve parameters (slope and maximum absorbance), the area under the sigmoid curve is used as a score for nanoweb formation (Figure 17). The nanoweb formation factor (Nf) is considered as the point where half of the available polymers associate with the surfactant.

[0462] In summary, this automated method interprets nanoweb formation based on an S-shaped fit of parameters derived from absorbance versus surfactant concentration plots. The area under the S-curve (AUC) is used to calculate a nanoweb score. If no S-shape is detected, nanoweb formation is considered to have not occurred. Each polymer and surfactant combination is scored individually. The resulting AUC values ​​are converted to a range of 0 to 1. The resulting score indicates nanoweb formation. The converted score encompasses two aspects. First, it covers the height of the absorbance curve, which can indicate the formation of a relatively large amount of nanoweb. Second, it covers the range of surfactant concentrations that contribute to nanoweb formation (for a fixed polymer concentration).

[0463] The results are shown in Figure 17.

[0464] Example 17

[0465] Nanonetwork formation occurs in the presence of anionic and nonionic surfactants.

[0466] In this section, the influence of the chemical structure of surfactant head groups on nanoweb formation was investigated. Nanowebs formed with surfactants containing various nonionic and ionic head groups were examined. Head groups were classified by the functional groups that form the main interactions with water in solution, the number of repeating functional groups, and the bonds with hydrophobic alkyl chains. Nanoweb formation was examined with all other surfactants tested (Tables 12A-D) except for the combinations shown below (Tables 13 and 14).

[0467]

[0468]

[0469]

[0470]

[0471]

[0472]

[0473]

[0474]

[0475]

[0476]

[0477]

[0478]

[0479]

[0480]

[0481]

[0482]

[0483]

[0484]

[0485]

[0486]

[0487]

[0488]

[0489]

[0490]

[0491]

[0492]

[0493]

[0494]

[0495]

[0496]

[0497]

[0498]

[0499]

[0500]

[0501]

[0502]

[0503]

[0504]

[0505]

[0506]

[0507]

[0508]

[0509]

[0510]

[0511]

[0512]

[0513]

[0514]

[0515]

[0516]

[0517]

[0518]

[0519]

[0520]

[0521]

[0522]

[0523]

[0524]

[0525]

[0526]

[0527]

[0528]

[0529]

[0530] Example 18

[0531] In pure surfactant aggregate systems, nanonetwork formation is preferably achieved with alkyl chain length > C7.

[0532] In this section, the effect of surfactant alkyl chain length on nanonetwork formation was investigated. A wide range of surfactant aggregate sizes were used. The surfactants are listed in Table 15, including surfactant aggregate sizes. Despite the small alkyl chains, light scattering measurements of these surfactant aggregates show a wide range of surfactant aggregate sizes. However, no nanonetwork formation occurred for all five surfactants except 1,2-hexanediol and SMA 725. This was true even when testing relatively small polymer particle sizes.

[0533] Therefore, the results in Table 15 indicate that, in some cases, factors other than relative size ratios can influence nanonetwork formation. Here, the results show that for surfactant aggregates consisting solely of surfactants containing fewer than eight carbons in their straight-chain hydrophobic alkyl chains, nanonetwork formation does not occur within the studied time range.

[0534]

[0535]

[0536] Example 19

[0537] Nanonetworks are preferably formed from aggregates of soluble or emulsified surfactants with a diameter larger than the theoretical compact diameter of the SMA polymer.

[0538] Previous results clearly show that fatty acid-containing surfactants such as VDISTILL DV53 and VDISTILL DV63 form oily substances and are therefore immiscible with water. Consequently, the surfactant aggregate diameter could not be measured by dynamic light scattering because the surfactants do not form stable emulsions in water. Insoluble fatty acid oils can be converted into soluble surfactant aggregates by soap conversion or solubilization with other surfactants.

[0539] Nonionic surfactants with branched hydrophilic head groups predominate in nonionic surfactants that do not form nanonetworks but meet the rules for nanonetwork formation. Despite having a measured surfactant aggregate diameter larger than the tested polymer, some nonionic surfactants still fail to form nanonetworks. Among these surfactants, disproportionately, polysorbate (TWEEN) is a notable exception. TM The large head groups may contain polyglycerol (PGL) or other polyglycerol (PGL) head groups. These large head groups may inhibit the interaction between the polymer and the alkyl chains of the surfactant. Another possible explanation is that the large head groups produce non-spherical surfactant aggregate shapes, which would result in pseudo-surfactant aggregate diameters or prevent polymer association. Yet another possible explanation is that these surfactants do associate with the SMA polymer, but they are unstable after precipitation, and the surfactant can dissociate back into solution.

[0540] The effect of branched hydrophilic head groups can be Figure 20The results are visually illustrated. Compared to all other surfactant classes, the large polyglycerol-10 head group surfactants exhibit a unique trend. Besides the nanonetwork score increasing with decreasing HLB value, the nanonetwork score also increases with more hydrophilic surfactants. However, because all polyglycerol-10 surfactants form large surfactant aggregates, they still form nanonetworks with at least one of the tested polymers.

[0541] Some false positive results can be partially explained by errors in size analysis methods and the concentration dependence of surfactant-associated aggregate formation. For example, for many surfactants, increasing concentration leads to the formation of larger structures, such as worm-like micelles, disordered aggregates, gels, and even bilayers (Gao, J., Ge, W. & Li, J.Sc.China Ser.B-Chem.(2005)48:470.https: / / doi.org / 10.1360 / 042004-71). When performing DLS measurements on surfactants in this work, the surfactant solution was continuously diluted and measured until the optimal PDI was obtained. This means that the surfactant concentration during size analysis can be anywhere from 1% wt / vol to 0.01% wt / vol, depending on the surfactant. However, in the nanonet formulation experiments described and used in this paper using Method #1, the polymer and surfactant were mixed together in a concentrated stock solution (1%) before dilution and precipitation in the nanonet formulation titration. This ensures that the surfactant aggregates remain above their critical micelle concentration; thus, they interact with the polymer prior to dilution and precipitation. As a result, the effective concentration and diameter of the surfactant aggregates in the nanonetwork formation experiments can be significantly higher than the concentration and recorded size when measuring the surfactant size.

[0542] Several commercially available surfactants, particularly Biosoft, Bioterge, Cedepal, and Ninate 411, showed measured surfactant aggregate diameters larger than the theoretical polymer diameter for each tested polymer (Table 15). Therefore, nanoweb formation with all tested polymers was expected using these surfactants. However, while each surfactant could be formulated into a nanoweb with at least one polymer, other factors resulted in not all combinations producing nanoweb formation. For example, only polymers that formed nanowebs with the following surfactant were selected: Stepan Bio-Soft D-40. TM Stepan Bio-TergeAS-40 TM Cedepal TD-403MFLD TM and Ninate 411 TMSurfactants (Table 15). Additionally, Ninate 411 TM The surfactants showed no indication of forming nanonetworks with the following polymers: SMA-IBE and SMA cumene (Table 15). For both polymers, a significant difference was observed between the measured DLS and the theoretical particle size (DLS was 5.8 nm, theoretical particle size was 2.8 nm). Furthermore, these two polymers contained different ratios of hydrophobic to hydrophilic functional groups in their repeating block units.

[0543] Therefore, the tendency of polymer particle size or block hydrophobicity is unlikely to prevent the use of Ninate 411. TM The formation of nanonetworks. More likely, the commercially available surfactants tested are not pure chemicals and therefore may have a second component that alters polymer behavior or complicates size measurements. For example, two different Bio-Terge formulations are available commercially, Bio-Terge 40S or Bio-Terge 40K, both containing C 14 -C 16 Sodium olefin sulfonate is the main active ingredient. However, while the 40S formulation is suitable for preparing stable microemulsions, the 40K formulation is only recommended as a general detergent (manufacturer's product list).

[0544] Undisclosed additives, solvents, or residues from surfactant preparation methods in these formulations may negatively impact nanoweb formation. Inaccurate surfactant size data may also exist. This can explain some discrepancies between predictions and actual observations in nanoweb formation experiments between different polymers. For example, if a given polymer-surfactant combination cannot efficiently form a nanoweb, the presence of stabilizing ligands or co-surfactants outside the surfactant micelles (e.g., in Ninate 411) may be a contributing factor. TM In the case of isopropylamine, it may shield surfactant aggregates and inhibit the formation of nanonetworks.

[0545] The size difference between surfactant aggregates and amphiphilic polymer particles driven by hydrophobic effects has been tested using seven different polymers and over 50 unique surfactants. The data strongly support the claim that the formation of nanowebs requires surfactant aggregates with a diameter larger than the smallest monomer particle size associated with the surfactant aggregates. Furthermore, the following strongly favor the formation of nanowebs using the tested polymers: (1) the surfactant has more than 7 carbons in the hydrophobic alkyl chain, (2) the surfactant is water-miscible, and (3) the surfactant has a relatively small head group. In summary, the results indicate that the design of nanowebs can be enhanced by selecting amphiphilic block copolymers whose length can be based on the size of the surfactant aggregates. Most of the formed nanowebs showed an increase in diameter relative to the starting polymer. Figure 18 ).

[0546] Example 20

[0547] Polymer composition affects the capture of surfactants in the nanonetwork.

[0548] The effects of surfactants and parameters, including the degree of water miscibility, on the formation of nanowebs were investigated. The study found that factors influencing the formation of the desired nanowebs included: a water-soluble amphiphilic block copolymer with XnYm block stoichiometry. X is an anionic or nonionic hydrophilic functional group. Y is a hydrophobic functional group. In the polymer formula, n = 1 and m = 1, 2, or 3.

[0549] The nanoweb library was expanded by testing polymers with different functional groups. Factors explored included polymer length and the ratio of polymer functional groups (two different hydrophobic chemical groups). The polymers tested are summarized in Table 16. For all tested polymers, nanowebs could be formed using surfactant aggregates larger than the particle size of the dense polymer. Figure 19 The maximum S-shaped AUC score for nanonetwork formation was observed using polymers with a styrene-maleic acid ratio of 2:1, followed by a 3:1 ratio, and then a 1:1 ratio. For nanonetwork formation, relatively shorter polymers generally had higher scores.

[0550]

[0551] Not all possible combinations of surfactants and polymers are likely to form nanowebs within the timeframe of the screening methods employed (see Example 15). Of the 116 polymer-surfactant combinations, 33 did not produce a score indicating nanoweb formation by screening method #1 (see Reagents and Materials Examples 15-21). These results (no nanoweb formation) could be predicted using the teachings described herein. However, 5.4% (14 / 306) of the formulations screened in method #2 (see Reagents and Materials Examples 15-21) produced a score indicating nanoweb formation. However, nanoweb formation will not be predicted based solely on relative size. Surfactant aggregates have a smaller diameter than polymer particles. Therefore, nanoweb formation will not be predicted using the teachings described herein. These false positive results can be attributed to the fact that in screening method #1, a relatively small increase in absorbance has been interpreted as the formation of an S-shaped curve by a developed computer model. This result would be a low, but still positive, score indicating nanoweb formation; even when no nanoweb formation is observed. False negative results can be attributed to: insufficient titration point; in some cases, nanonetwork formation occurs only in one test proportion, meaning the association window is very small. In other cases, the titration curve only begins to increase at very high titration concentrations. In the current experiment, these signals will be missed.

[0552] ROUT method for statistical analysis of outlier identification

[0553] A rationale for removing some data points initially identified by the model was also developed. For example, results were further screened to remove those with low formation factor Nf and absorbance values ​​less than 0.2 (Tables 9 and 10). Outliers in the dataset of surfactant polymer assemblies used for nanonet formation were analyzed by screening method #4 (see Reagents and Materials Examples 15-21). The method used was similar to that described in Motulsky, HJ, Brown, and REDetecting in Outliers When Fitting Data With Nonlinear Regression – A New Method Based On Robust Nonlinear Regression And The False Discovery Rate. BMC Bioinformatics 7, 123 (2006). Outliers in surfactant size were identified in both positive-scoring and negative-scoring nanonet datasets using the ROUT method.

[0554] Therefore, the screening plus ROUT analysis reduced the number of false positive results to 9 out of 192. This means that false positive scores for nanonet formation were obtained in only 9 out of 192 cases.

[0555] Factors other than size relationships can also explain this result. These factors may include: (1) the number of carbon atoms in the surfactant alkyl chain, (2) the surfactant's water solubility, and (3) the surfactant's hydrophobic lipid balance. Additionally, there may be several sources of error in surfactant aggregate and polymer particle size measurements. Other reasons for the difference between expected and observed results may include: (1) surfactant composition, (2) surfactant purity, (3) polymer composition, (4) molecular weight distribution, (5) surfactant head group size, (6) surfactant packing parameters, and (7) comonomer distribution. For example, in several cases, our measurements of polymer elongation and molecular weight differed from those provided by commercially available samples. A more detailed discussion of these other factors follows.

[0556] The number of carbon atoms in the alkyl chain of a surfactant.

[0557] Of the 62 surfactants tested, five contained small hydrophobic segments (straight-chain alkyl chains with fewer than seven carbons). Interestingly, using method #1 (titration determination, Table 15), none of these five surfactants produced scores indicating nanonetwork formation. This was the case for all polymers tested, except for surfactants 1,2-hexanediol and SMA-725.

[0558] DLS measurements of these low-carbon-number surfactant aggregates revealed a wide range of surfactant aggregate sizes. The latter results indicate that nanonetwork formation does not occur for aggregates consisting solely of surfactants containing fewer than 8 carbons in their straight-chain hydrophobic alkyl chains. Therefore, a more general conclusion is that nanonetwork formation is more likely to occur when the surfactant has more than 7 carbons in its alkyl chain when measured as pure surfactant aggregates. The effect of alkyl chain number can be further visualized by examining nanonetwork formation with selected surfactant head groups and different alkyl chains. Figure 21 In almost all cases, an increase in the number of alkyl chains led to an increase in the nanonetwork score and an increased likelihood of forming a nanonetwork with the polymer being tested. Figure 21 Similarly, hydrophilic head groups generally show an inverse effect on nanonet scores: as HLB values ​​increase due to the increasing number of hydrophilic head groups, nanonet scores decrease (AD). Figure 21E and F). This effect of alkyl chain length and HLB in surfactants on nanonetwork scores, as well as compatibility with different polymers, suggests that nanonetwork formation occurs best at a 2:1 block ratio. The number of nanonetworks that can be formed generally decreases as the polymer composition shifts from 2:1 to 3:1 or 1:1. Furthermore, with decreasing polymer length, nanonetworks can be formed using smaller and more hydrophilic surfactant aggregates (high HLB values). The reverse may also be true: the more hydrophobic the surfactant, the larger the preferred polymer and the more hydrophobic blocks. For example, 1,2-hexanediol or VDISTILL 53 with calculated HLB values ​​of 7.9 and 1 (using the Davies method, JTDavies, EKRideal, Interfacial Phenomena, Academic Press, New York, 1961, p. 371.) TM Found only in the most hydrophobic polymers; SMA-725 TM Association.

[0559] Example 21

[0560] Optimizing the formation of nano-network libraries:

[0561] For the chemical treatment of water, downstream effluents need to be virtually uncontaminated by any introduced chemicals. Therefore, in nanoweb formulations, most surfactants must bind to the polymer to minimize any residual surfactant downstream during treatment. To determine the optimal amount of surfactant, titration data for a given surfactant can be used. The midpoint (also known as Nf) on each titration curve represents the half-maximum surfactant binding. The midpoint is calculated according to Method #4 (see Reagents and Materials Examples 15-21). At this concentration, a polymer excess is expected, resulting in minimal surfactant presence in solution, and at least half of all polymers are expected to form a nanoweb complex. For a given polymer, surfactants with a high midpoint (>500 ppm) are considered to have low affinity, and therefore these combinations have not been identified as forming stable nanowebs.

[0562] To better identify stable nanonetworks, the absorption peak heights of each surfactant and polymer combination were filtered to 0.2 and higher to obtain an optimized nanonetwork library. In the titration data, low peak absorbance indicates few surfactant aggregates trapped by the polymer, thus representing an inefficient nanonetwork combination and potentially leading to high concentrations of residual surfactant after removing any formed nanonetworks. Based on these results, it can be understood that these filtered combinations can still form small amounts of nanonetwork complexes, but they are not optimal, and other polymers may be more suitable.

[0563] Using this method, a nanonetwork library containing approximately 199 stable, optimized nanonetworks was identified. The nanonetwork library comprises a wide range of anionic and nonionic surfactants with C8 to C966 nanometers. 18 The lengths of the straight-chain alkyl chains vary. The hydrophilic head groups included in the nanonetwork library are diverse in nature, including sulfonates, phosphates, phosphine oxides, monosaccharides, disaccharides, thioesters, amino acids, diols, and polyglycerols. The complete nanonetwork library is recorded in Tables 9 and 10.

[0564]

[0565]

[0566]

[0567]

[0568]

[0569]

[0570]

[0571]

[0572] Example 22

[0573] Proof-of-concept for screening nanonet libraries for chelating divalent metal ions zinc and copper present in seawater

[0574] Metals in seawater pose a threat to aquatic systems and organisms. Removing heavy metals from seawater or wastewater typically involves precipitating dissolved metal ions followed by filtration. However, these methods can be challenging because they require controlling the pH of the seawater.

[0575] A library of nanonetworks containing anionic and nonionic surfactants was screened for the removal of zinc and copper ions from seawater doped with zinc and copper ions (see Reagents and Materials Examples 15-21, Method #3). All hydrolyzed SMA-containing polymers showed excellent removal of Cu ions from seawater. 2+ Metal ion removal, especially with polymer SMA-2000 TM SMA-2021 TM and SMA-725 TM Surfactants with head groups containing sulfonate and amino acids ( Figure 22 Conversely, nanonets with DIBMA exhibit residual Cu in seawater. 2+ Metal ions (<10ppm). Figure 23An example is shown using a nonionic surfactant and SMA-2000. TM SMA-2021 TM SMA-cumene-terminated TM and SMA-725 TM Nano-mesh from seawater with excellent Cu 2+ Metal ion removal. Conversely, with SMA-3000 TM and DIBMA TM The nanomesh exhibits low efficiency in removing metal ions. In summary, nanomembranes with anionic surfactants are inefficient at removing zinc metal ions from seawater, especially when used with SMA-3000. TM and DIBMA TM combination( Figure 24 Interestingly, the surfactant N-dodecanoyl-L-histidine is related to SMA-2000. TM SMA-725 TM and SMA-cumene-terminated TM Combination and SMA-725 TM Combining with dodecane-1-sulfonic acid in Zn 2+ Most effective for removing metal ions ( Figure 24 It contains nonionic surfactants and SMA-2000. TM and SMA-cumene-terminated TM Nanomesh removes zinc metal ions, where residual Zn in the solution 2+ Less than 5 ppm Figure 25 It features SMA-3000. TM and DIBMA TM Nanonets are inefficient at removing metal ions. This work demonstrates that novel water treatment agents with specificity for single metals can be rapidly identified through screening a library of nanonets.

[0576]

[0577]

[0578]

[0579]

[0580]

[0581]

[0582]

[0583]

[0584]

[0585] Example 23

[0586] Nanonetworks formed using derived SMA polymers.

[0587] To demonstrate that alternative hydrophilic functional groups can be used to fabricate nanowebs, SMA-2000 was fabricated by reacting acid anhydrides with ethanolamine. TM Derivatization. The resulting polymer is compatible with all three Triton series surfactants (TX-100). TM TX-305 TM TX-45 TM The study confirmed that derivative polymers with alternative hydrophilic functional groups can also be used to form nanowebs.

[0588] Triton TM The X series uses a derivative of SMA 2000 at a concentration of 200 ppm in the concentration range of 1000-0 ppm. TM Polymer titration; activation of the nanonet with 10 μL of HCl

[0589]

[0590]

[0591]

[0592]

[0593] Example 24

[0594] The effect of polymers on the settling velocity of nanofiber flocs.

[0595] Experimental protocol

[0596] 3 mL of 4000 ppm Ca, prepared from calcium chloride (83%-87%, Downflake). 2+ The solution was added to the Ebendorf tube.

[0597]

[0598] Polymer-surfactant nanomesh composites were prepared by adding a 2% polymer solution to a 1% surfactant solution at a polymer-surfactant ratio of 2.5:1. To bind the nanomesh to free calcium ions, 100 μL of a polymer-surfactant mixture (97 ppm surfactant, 473 ppm polymer) was added to a calcium solution, after which clear white flocculents were observed in the solution.

[0599] To test the effect of adding the polymer alone, 71 μL of a 2% polymer solution (473 ppm polymer) was added to the calcium solution.

[0600] Shake the mixture at 600 RPM (gentle shaking) for 1 minute. Gentle shaking ensures that floc breakage is minimized during mixing, as this will increase the time required for batch settling.

[0601] Quartz cuvettes used to hold samples must be cleaned five times with deionized (DI) water and then manually dried with lens paper until the outer surface is dry and optically clean.

[0602] After mixing for 1 minute, immediately transfer the flocculated suspension to a clean quartz cuvette, and then begin time tracking. Record video for 25 minutes at a frequency of 0.2 Hz.

[0603] Calculation of batch settlement parameters

[0604] Write a Python script to track the settling of flocs. Consider the target area (ROI) as the region of the floc bed after 25 minutes of settling. To do this, manually select a box spanning the inner wall of the cuvette and the bottom of the meniscus.

[0605] From this point, the image processing program automatically extracts the location of the interface between the clarified liquid phase and the settled consolidated bed. The height of the consolidated bed can be calculated, and a new ROI for the settling region can be generated for subsequent analysis.

[0606] Within this new ROI, the average grayscale pixel intensity can be calculated over time; since the flocculent is white in color (opposite to a dark black background), this value is expected to increase during settling. This value can be interpreted as the amount of flocculent settling at the bottom of the cuvette.

[0607] To output a single, quantifiable target parameter from a series of images tracking sedimentation, an sigmoid function is fitted to the apparent flocculant sedimentation data.

[0608] exist Figure 26 An example of this curve fitting for apparent settlement is shown in the figure.

[0609] After curve fitting, t can be reported. 50 The value (center of the S-shape) is used as an indicator of settling velocity. Depending on the nature of phase separation, this can also be used as an indicator of floc size (faster settling = lower t). 50 ).

[0610] result

[0611] Polymer selection directly affects settling velocity.

[0612] t of three polymers50 Legend is shown in Figure 27 middle.

[0613] Polymer selection significantly and directly affects settling velocity. SMA-725 TM It has the highest molecular weight, and according to this principle, it is expected to settle the fastest.

[0614] Different polymers SMA-725 TM With SMA-3000 TM There are differences in settling velocities. Generally, longer polymers settle significantly faster than shorter polymers (SMA-725). TM SMA-2000 TM / 3000 TM However, in these experiments, SMA-2000 TM Compared to SMA-3000 TM It settles faster, but SMA2000 TM The polymers are slightly shorter. The lack of this correlation between polymer length and settling velocity suggests the existence of other polymer properties besides polymer length that can influence the phase separation behavior of nanonets. This determination indicates that effective nanonet design requires not only large surfactant aggregates and small polymers; polymer size and chemical properties will also significantly affect nanonet removal in wastewater treatment processes.

[0615] Example 25

[0616] Preparation and characterization of nano-Fe:

[0617] Heat 100 L of a 1.5 M stock solution of KOH to 95 °C. Add 10 kg of pre-ground SMA 725 to the solution while vigorously mixing. Let the solution stand for 3 hours to hydrolyze, during which time pump 4 kg of oleic acid into the mixture. Mix the solution at 95 °C. After 1 hour, add 10 L of preheated 20% polyglycerol-10-stearate solution to the mixture. Cool the solution to 60 °C while continuing to mix, at which point pump the solution through a 1-micron filter to remove any unhydrolyzed polymer. Then add distilled or deionized water to the solution to compensate for any evaporation loss.

[0618] Eleven batches of nanomesh Fe were prepared as described, and the particle size and viscosity of each batch were measured. The nanomesh batches are recorded in Table 24 below. The particle size was measured by dynamic light scattering on a Malvern NanoZS and calculated based on the intensity value. The viscosity was measured at 23°C on a Brookfield VII rheometer.

[0619]

[0620]

[0621] Example 26

[0622] Nano-mesh iron is used to treat extracted water during the water treatment process.

[0623] In the following examples, produced water from the Permian Basin in Texas, USA, was treated with a batch of 7-nanometer Fe from Example 25.

[0624] The incoming produced water was pumped from a 1000L conveyor through a 484Mazzei Venturi ejector at a flow rate of 4 GPM. 50 ppm of nanomesh was added to the ejector while air was added at approximately 3 L / min. The water passed through a reaction tank and then into a flocculation circuit. The water then entered a dissolved air flotation unit, where the nanomesh iron complex was floated to the surface and removed from the water. Iron levels, turbidity, total dissolved solids, redox potential, and alkalinity were displayed. Figure 28 In A-28E.

[0625] Example 27

[0626] Nano-mesh iron is used to treat effluent during water treatment with the addition of anionic flocculants.

[0627] The incoming produced water was pumped through a 784 Mazzei Venturi injector at a flow rate of 8 GPM. 30 ppm of nano-mesh Fe from batch 11 of Example 25 was actively added to the Venturi injector using a peristaltic pump. The treated fluid then flowed into a mixing tank, which was weakly aerated by a recirculation jet from the effluent of the treatment column. To aid in iron capture, the mixing tank was rapidly mixed using a dynamic high-shear mixer. The treated fluid exited the mixing tank, at which point 1 ppm of anionic flocculant was added. The treated fluid then passed through a series of high-speed and low-speed mixing chambers to enhance flocculant deployment and flocculation of the nano-mesh iron complex. The treated fluid then entered a flotation chamber and was floated to the surface by the addition of dissolved air. The final effluent exited the DAF through a series of weirs and was pumped through a final polished filter with an average pore size of 20 micrometers. The inflow and outflow iron and bacteria levels of the water treated by this method are shown in Tables 25 and 26 below.

[0628]

[0629]

[0630]

[0631] Example 28

[0632] The oxidation requirement is reduced by adding nano-mesh iron.

[0633] Removing ferrous iron from the solution may reduce the overall demand for oxidizing chemicals in water treatment during oilfield operations. To test this hypothesis, ferrous iron solutions were treated with and without nanomesh, followed by treatment with sodium chlorite. The solutions were filtered, and a measured amount of chlorine dioxide was added to the filtrate. Increasing the amount of nanomesh resulted in a significant increase in oxidant residue, indicating the removal of the oxidation requirement in the system.

[0634] Figure 29 A and Figure 29 B shows another side-by-side comparison of iron removal using nanomesh. First, treatment with a specified concentration of NaClO2 supplemented with 50 ppm Fe was performed. 2+ The extracted water was then treated sequentially with specified doses of Fe nanofiber (0, 10, 20, 40 ppm, as increasingly lighter stripes). The solution was mixed by inversion and allowed to stand at room temperature for 5 minutes (without aeration). The resulting solution was gravity filtered (using a 10-micron cellulose filter), and the iron content of the filtrate sample was analyzed by ferrazine determination (A). The filtrate was then treated with 25 ppm ClO2 and incubated for 5 minutes, after which the residual ClO2 was measured (B).

[0635] Although various embodiments of the invention have been disclosed herein, many adaptations and modifications can be made within the scope of the invention based on common knowledge to those skilled in the art. Such modifications include replacing any aspect of the invention with known equivalents in order to obtain the same results in substantially the same manner. Numerical ranges include numbers that define the range. Furthermore, numerical ranges are provided such that, in addition to the individual values ​​specifically listed in the ranges where no range is provided, a range of values ​​is also listed. The word “comprising” is used herein as an open-ended term, substantially equivalent to the phrase “including but not limited to,” and the word “containing” has the corresponding meaning. As used herein, the singular forms “a,” “an,” and “the” include a plural of references unless the context clearly indicates otherwise. Thus, for example, reference to “one thing” includes more than one such thing. References cited herein are not an admission that such references are prior art to the invention. Furthermore, the material appearing in the background section of the specification is not an admission that such material is prior art to the invention. Any priority document incorporated herein by reference is as if each individual priority document were specifically and individually indicated by reference to this document and as if it were set forth in detail herein. The present invention includes all embodiments and variations substantially as described above and with reference to the embodiments and drawings.

Claims

1. A kit for chelating non-aqueous fractions from aqueous solutions, the kit comprising: a) Surfactant aggregates with an average aggregate diameter; and b) A polymer having an average particle size equal to or less than the average aggregate diameter, wherein the polymer is selected from: poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 3:1 and Mw of 130,000 g / mol, poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 2:1 and Mw of 7,500 g / mol, poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 3:1 and Mw of 9,000 g / mol, poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 2:1 and Mw of 22,000 g / mol, polymethacrylate, diisobutylene-co-maleic acid, styrene-urethane block copolymers, and styrene-maleimide block copolymers; and c) Precipitating agent, The condition is that the surfactant is selected from: Triton X-100 TM Triton X-305 TM When N-dodecyl-β-D-maltodextrin (DDM), sodium oleate, sodium cholate, sodium deoxycholate (DOC), β-octyl glucoside (β-OG), or lauryl dimethylamine n-oxide (LDAO) is present, the polymer is not selected from: SMA-2000 TM SMA-2021 TM And diisobutylene-co-maleic acid (DIBMA).

2. The kit of claim 1, wherein the precipitant is selected from: cations, acids, and mixtures thereof.

3. The kit of claim 1, wherein the precipitant is selected from: acids, divalent cations, trivalent cations and mixtures thereof.

4. The kit of claim 1, wherein the precipitant is selected from: acetic acid, malic acid, citric acid, tartaric acid, fumaric acid, lactic acid, hydrochloric acid, sulfuric acid, and phosphoric acid.

5. The kit according to any one of claims 1 to 4, wherein the surfactant is selected from: anionic surfactants, nonionic surfactants, sugar-derived surfactants, glycidyl-derived surfactants, fatty acid alcohol-derived surfactants, sugar polyoxyethylene combination surfactants, sugar ester surfactants, sulfonated sugar surfactants, aldose amide surfactants, amide sugar surfactants, amino alcohol surfactants, amino acid surfactants, polyol surfactants, 1,2-diol surfactants, and amphoteric surfactants.

6. The kit according to any one of claims 1 to 4, wherein the surfactant is a nonionic surfactant.

7. The kit according to any one of claims 1 to 4, wherein the surfactant is an ionic surfactant.

8. The kit according to any one of claims 1 to 4, wherein the surfactant is an anionic surfactant.

9. The kit according to any one of claims 1 to 4, wherein the surfactant has a neutral charge.

10. The kit according to any one of claims 1 to 4, wherein the surfactant is an uncharged surfactant.

11. The kit according to any one of claims 1 to 4, wherein the surfactant is soluble in water.

12. The kit according to any one of claims 1 to 4, wherein the surfactant is insoluble in water.

13. The kit of claim 1, wherein the surfactant is selected from: octylphenol ethoxylate, nonylphenol ethoxylate, polyglycerol-10-oleate, polyglycerol-10-laurate 1, polyglycerol-10-stearate, polyglycerol-10-laurate 2, polyglycerol-10-palmitate, Triton X-45 TM Triton X-100 TM Triton X-305 TM Sodium oleate, LDAO and their mixtures.

14. The kit of claim 1, wherein the surfactant is a mixture of polyglycerol-10-palmitate and sodium oleate.

15. The kit of claim 1, wherein the surfactant is a mixture of polyglycerol-10-palmitate and potassium oleate.

16. The kit of claim 1 and any one of claims 13 to 15, wherein the polymer is SMA-725. TM .

17. The kit according to any one of claims 1 to 4 and 13-15, wherein at least a portion of said polymer is hydrolyzed.

18. Nanonet, comprising: a) Surfactant aggregates with an average aggregate diameter; and b) A polymer having an average particle size equal to or less than the average aggregate diameter, wherein the polymer is selected from: poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 3:1 and Mw of 130,000 g / mol, poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 2:1 and Mw of 7,500 g / mol, poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 3:1 and Mw of 9,000 g / mol, poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 2:1 and Mw of 22,000 g / mol, polymethacrylate, diisobutylene-co-maleic acid, styrene-urethane block copolymers, and styrene-maleimide block copolymers. The condition is that the surfactant is selected from: Triton X-100 TM Triton X-305 TM When N-dodecyl-β-D-maltodextrin (DDM), sodium oleate, sodium cholate, sodium deoxycholate (DOC), β-octyl glucoside (β-OG), or lauryl dimethylamine n-oxide (LDAO) is present, the polymer is not selected from: SMA-2000 TM SMA-2021 TM And diisobutylene-co-maleic acid (DIBMA).

19. The nanomesh of claim 18, wherein the nanomesh has a diameter larger than the average polymer particle size.

20. The nanomesh of claim 18 or 19, wherein the surfactant is selected from: anionic surfactants, nonionic surfactants, sugar-derived surfactants, glycidyl-derived surfactants, fatty acid alcohol-derived surfactants, sugar polyoxyethylene combination surfactants, sugar ester surfactants, sulfonated sugar surfactants, aldose amide surfactants, amide sugar surfactants, amino alcohol surfactants, amino acid surfactants, polyol surfactants, 1,2-diol surfactants, and amphoteric surfactants.

21. The nanonet of claim 18 or 19, wherein the surfactant is a nonionic surfactant.

22. The nanonet of claim 18 or 19, wherein the surfactant is an ionic surfactant.

23. The nanonet of claim 18 or 19, wherein the surfactant is an anionic surfactant.

24. The nanonet of claim 18 or 19, wherein the surfactant has a neutral charge.

25. The nanonet of claim 18 or 19, wherein the surfactant is an uncharged surfactant.

26. The nanonet of claim 18 or 19, wherein the surfactant is soluble in water.

27. The nanonet of claim 18 or 19, wherein the surfactant is insoluble in water.

28. The nanomesh of claim 18 or 19, wherein the surfactant is selected from: octylphenol ethoxylate, nonylphenol ethoxylate, polyglycerol-10-oleate, polyglycerol-10-laurate 1, polyglycerol-10-stearate, polyglycerol-10-laurate 2, polyglycerol-10-palmitate, Triton X-45 TM Triton X-100 TM Triton X-305 TM Sodium oleate, LDAO and their mixtures.

29. The nanonet of claim 18 or 19, wherein the surfactant is a mixture of polyglycerol-10-palmitate and sodium oleate.

30. The nanonet of claim 18 or 19, wherein the surfactant is a mixture of polyglycerol-10-palmitate and potassium oleate.

31. The nanomesh of claim 18 or 19, wherein the polymer is SMA-725. TM .

32. The nanonet of claim 18 or 19, wherein at least a portion of the polymer is hydrolyzed.

33. The nanonet of claim 18 or 19, further comprising a chelated non-aqueous portion.

34. The nanonet of claim 33, wherein the chelated non-aqueous portion is an iron portion.

35. A method for chelating a non-aqueous portion from an aqueous solution, the method comprising: a) Adding surfactant aggregates having an average aggregate diameter to the aqueous solution containing the non-aqueous portion; as well as b) Adding a polymer having an average particle size equal to or less than the average aggregate diameter to the aqueous solution containing the non-aqueous portion, wherein the polymer is selected from: poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 3:1 and an Mw of 130,000 g / mol; poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 2:1 and an Mw of 7,500 g / mol; poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 3:1 and an Mw of 9,000 g / mol; poly(styrene-co-maleic anhydride) with a styrene:maleic anhydride ratio of 2:1 and an Mw of 22,000 g / mol; polymethacrylate; diisobutylene-co-maleic acid; styrene-urethane block copolymer; and styrene-maleimide block copolymer. This results in a treated aqueous solution. The condition is that the surfactant is selected from: Triton X-100 TM Triton X-305 TM When N-dodecyl-β-D-maltodextrin (DDM), sodium oleate, sodium cholate, sodium deoxycholate (DOC), β-octyl glucoside (β-OG), or lauryl dimethylamine n-oxide (LDAO) is present, the polymer is not selected from: SMA-2000 TM SMA-2021 TM And diisobutylene-co-maleic acid (DIBMA).

36. The method of claim 35, further comprising adding a precipitant to the treated aqueous solution.

37. The method of claim 35 or 36, further comprising mixing.

38. The method of claim 35 or 36, further comprising removing solid particles from the treated aqueous solution.

39. The method of claim 38, wherein the removal of solid particles comprises at least one selected from: filtration, centrifugation, gravity separation, flotation, skimming, and electromagnetic attraction.

40. The method of claim 35 or 36, wherein the surfactant is selected from: anionic surfactants, nonionic surfactants, sugar-derived surfactants, glycidyl-derived surfactants, fatty acid alcohol-derived surfactants, sugar polyoxyethylene combination surfactants, sugar ester surfactants, sulfonated sugar surfactants, aldose amide surfactants, amide sugar surfactants, amino alcohol surfactants, amino acid surfactants, polyol surfactants, 1,2-diol surfactants, and amphoteric surfactants.

41. The method of claim 35 or 36, wherein the surfactant is a nonionic surfactant.

42. The method of claim 35 or 36, wherein the surfactant is an anionic surfactant.

43. The method of claim 35 or 36, wherein the surfactant has a neutral charge.

44. The method of claim 35 or 36, wherein the surfactant is an uncharged surfactant.

45. The method of claim 35 or 36, wherein the surfactant is soluble in water.

46. ​​The method of claim 35 or 36, wherein the surfactant is insoluble in water.

47. The method of claim 35, wherein the surfactant is selected from: octylphenol ethoxylate, nonylphenol ethoxylate, polyglycerol-10-oleate, polyglycerol-10-laurate 1, polyglycerol-10-stearate, polyglycerol-10-laurate 2, polyglycerol-10-palmitate, Triton X-45 TM Triton X-100 TM Triton X-305 TM Sodium oleate, LDAO and their mixtures.

48. The method of claim 35, wherein the surfactant is a mixture of polyglycerol-10-palmitate and sodium oleate.

49. The method of claim 35, wherein the surfactant is a mixture of polyglycerol-10-palmitate and potassium oleate.

50. The method of any one of claims 35 and 47 to 49, wherein the polymer is SMA-725. TM .

51. The method of any one of claims 35-36 and 47-49, wherein at least a portion of the polymer is hydrolyzed.

52. A method for chelating a non-aqueous portion from an aqueous solution, the method comprising adding a nanomesh of any one of claims 18 to 34 to the aqueous solution containing the non-aqueous portion, thereby forming a treated aqueous solution.

53. The method of claim 52, further comprising adding a precipitant to the treated aqueous solution.

54. The method of claim 52 or 53, further comprising mixing.

55. The method of claim 52 or 53, further comprising removing solid particles from the treated aqueous solution.

56. The method of claim 55, wherein the removal of solid particles comprises at least one selected from: filtration, centrifugation, gravity separation, flotation, skimming, and electromagnetic attraction.

Citation Information

Patent Citations

  • Fire-retardant polyamide composition having good heat resistance

    CA1338392C

  • Sucrose based surfactants and methods thereof

    US6184196B1

  • Aldonamides and their use as surfactants

    WO1994012511A1

  • Novel surfactants and novel emulsifiers made from disaccharides

    WO2006100091A1

  • Combination of flocculant with surfactant for wastewater treatment

    US20160214874A1